Toner and method for producing the same
By covering the aminoacetate resin on the surface of the ton agent particles and adopting a core-shell structure design, combined with high temperature and high pH processing steps, the problem of insufficient fixation performance of the existing ton agent at low temperatures is solved, efficient and rapid image formation is achieved, and image quality is improved.
Patent Information
- Application Number
- JP2021071560
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-04-21
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2041-04-21
AI Technical Summary
The fixing performance of the toner used in existing electro-optical image forming equipment is insufficient at low temperatures, making it difficult to achieve higher energy efficiency and faster printing speeds, and image quality is also difficult to ensure.
The toner with a softening point of 150°C or less is used. The surface of the toner particles is covered with amino acetate resin and has a core-shell structure. The core part contains styrene-acrylate resin and ester wax. The shell part contains only amino acetate resin. The positioning of the resin molecules is controlled through high temperature and high pH treatment steps to ensure that the resin is evenly distributed on the toner surface.
The stutter has excellent fixing performance at low temperatures, achieving improved energy efficiency and speed, and at the same time, image quality is guaranteed.
Smart Images

Figure 0007654456000022 
Figure 0007654456000023 
Figure 0007654456000024
Abstract
Description
[Technical field]
[0001] FIELD OF THE DISCLOSURE This disclosure relates to toners for use in electrophotography and methods for making toners. [Background technology]
[0002] In recent years, further energy saving is required for electrophotographic image forming apparatuses such as copiers and printers. Therefore, development of toners that can be fixed at lower temperatures has been promoted. Patent Document 1 discloses a toner in which viscoelastic properties are controlled by using a crystalline polyester. Patent Document 1 describes that the toner can suppress so-called cold offset, in which the toner adheres to the fixing film when passing through the fixing nip in an insufficiently melted state, and is fixed on the paper after going around the fixing film. It also describes that the viscoelastic properties can be easily controlled by dispersing such a crystalline material in the toner as a minute domain. Patent Document 2 discloses a toner that has excellent sharp melt properties and is compatible with low-temperature fixing properties and high-temperature storage stability by controlling the domains using a crystalline polyester and a melting point wax in the toner.
[0003] Conventionally, toners containing polyester resins have been widely used as materials for imparting functionality to toners from the viewpoint of diversity in resin design. For example, Patent Documents 3 and 4 disclose that in toners using polyester resin as a surface layer, the amount, composition, polarity, acid value, etc. of the polyester resin can be controlled to improve the chargeability. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2017-211648 A [Patent Document 2] JP 2017-207680 A [Patent Document 3] JP 2017-044982 A [Patent Document 4] JP 2016-142758 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, as there is an increasing demand for energy saving, there is a demand for further improvement in the low-temperature fixability of the toners described in Patent Documents 1-4.
[0006] The present disclosure provides a toner having excellent low-temperature fixing properties, and achieving energy savings, high speed and high image quality, and a method for producing the toner. [Means for solving the problem]
[0007] The toner of the present disclosure is a toner containing toner particles having a polyester resin, the softening point of the toner measured by a constant load extrusion type capillary rheometer is 150° C. or lower; the toner particles have the polyester resin within 100 nm from the surface of the toner particles, the polyester resin is an amorphous polyester resin, The toner particles are a core containing a styrene-acrylic resin and an ester wax; and A shell containing only the amorphous polyester resin having a core-shell structure having The shell covers the core, In a cross section of the toner observed with a transmission electron microscope, The shell has a thickness of 100 nm or more and 200 nm or less, the content of the ester wax is 5.00 parts by mass or more and 50 parts by mass or less relative to 100 parts by mass of the styrene-acrylic resin, the content ratio of the monomer unit represented by the following formula (B) in the amorphous polyester resin is 30.0 mass % or more and 50.0 mass % or less with respect to the mass of the amorphous polyester resin, The content ratio of the monomer unit represented by the following formula (C) in the amorphous polyester resin is 25.0 mass% or more and 50.0 mass% or less with respect to the mass of the amorphous polyester resin, The content ratio of the monomer unit represented by the following formula (D) in the amorphous polyester resin the ratio of the amorphous polyester resin to the total mass of the amorphous polyester resin is 1.0 mass% or more and 50.0 mass% or less, Time-of-flight secondary ion mass spectrometry ApplicableThe amount of ions is measured from the surface of the toner particles to a depth of 100 nm, and the amount of ions having the structure represented by the following formula (A) counted is divided by the total amount of ions counted to obtain the standard value: Applicable There is one or more peaks of the standard value within a range of 100 nm from the surface of the toner particle, When the standard value of the peak having the maximum standard value among the one or more peaks is defined as A(dmax) and the standard value on the surface of the toner particle is defined as A(0), the A(dmax) and the A(0) satisfy the following formulas (1) and (2): A toner characterized by About . 1.15≦A(dmax) / A(0)≦5.00 (1) 0.010≦A(0) (2)
[0008] [ka] [ka] (In formula (B), R 1 indicates a benzene ring.) [ka] (In formula (C), R 2 represents an ethylene group or a propylene group, x and y are each an integer of 1 or more, and the average value of x+y in the polyester resin is 2 to 10. [ka] (In formula (D), R 3 represents an ethylene group or a propylene group.
[0009] The toner manufacturing method of the present disclosure includes a step of obtaining resin particles containing a polyester resin, a dispersion step for obtaining a suspension in which the obtained resin particles are dispersed in an aqueous medium; a step of treating the suspension at pH (1) at 95° C. or higher, and then treating the suspension at pH (2); A cooling step of cooling the suspension treated in the treatment step at a cooling rate of 50° C. / min or more, the pH(1) and the pH(2) satisfy the following formulas (10) and (11): pH(1) <pH(2) (10) 6.0≦pH(2)≦10.5 (11) Effect of the Invention
[0010] The present disclosure can provide a toner having excellent low-temperature fixing properties, and achieving energy savings, high speed and high image quality, and a method for producing the toner. [Brief description of the drawings]
[0011] [Figure 1] Schematic diagram of the results of measuring the amount of ions from the surface of a toner particle to a depth of 100 nm using time-of-flight secondary ion mass spectrometry. [Diagram 2] Schematic diagram of the results of gradient polymer elution chromatography of the eluted components when acetonitrile was used as a poor solvent and chloroform was used as a good solvent for the chloroform-soluble fraction of polyester resin. (a) Two independent peaks, (b) two overlapping peaks, (c) one peak. [Diagram 3] FIG. 2 is a schematic diagram showing the shape of a domain. [Figure 4] Schematic diagram showing the state of domains. [Diagram 5] FIG. 2 is a schematic diagram showing an apparatus for modifying the surface of resin particles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] In the present disclosure, the description of a numerical range such as "XX or more and YY or less" or "XX to YY" means a numerical range including the lower and upper limits, which are the endpoints, unless otherwise specified. When a numerical range is described in stages, the upper and lower limits of each numerical range can be arbitrarily combined. The term "monomer unit" refers to the reacted form of a monomer substance in a polymer. For example, one section of carbon-carbon bond in the main chain of a polymer in which a polymerizable monomer is polymerized is considered to be one unit. The polymerizable monomer can be represented by the following formula (C).
[0013] [ka]
[0014] In formula (C), R A represents a hydrogen atom or an alkyl group (preferably an alkyl group having 1 to 3 carbon atoms, more preferably a methyl group); R B represents an optional substituent. The (meth)acrylic acid ester means an acrylic acid ester and / or a methacrylic acid ester. The crystalline resin means a resin that shows a clear endothermic peak in a differential scanning calorimeter (DSC) measurement.
[0015] As a result of extensive research, the inventors have found that by controlling the orientation state of the molecular chains of the polyester resin in the toner particles, it is possible to achieve excellent low-temperature fixing properties, energy savings, higher speeds, and higher image quality.
[0016] The toner of the present disclosure is a toner containing toner particles having a polyester resin, the softening point of the toner measured by a constant load extrusion type capillary rheometer is 150° C. or lower; the toner particles have the polyester resin within 100 nm from the surface of the toner particles, When the amount of ions is measured from the surface of a toner particle to a depth of 100 nm by time-of-flight secondary ion mass spectrometry, and the amount of counted ions having a structure represented by the following formula (A) is divided by the total amount of ions counted to define a standard value, one or more peaks of the standard value exist within a range of 100 nm from the surface of the toner particle, A toner, wherein when the standard value of the peak having the maximum standard value among the one or more peaks present is A(dmax) and the standard value on the surface of the toner particle is A(0), the A(dmax) and the A(0) satisfy the following formulas (1) and (2): 1.15≦A(dmax) / A(0)≦5.00 (1) 0.010≦A(0) (2)
[0017] [ka]
[0018] In the past, in toners having polyester resins near the surface of toner particles, the structure represented by formula (A) in the conventional polyester resins was randomly oriented and present, making it difficult to control. However, the present inventors have succeeded in controlling the orientation state of the structure represented by formula (A) by intensively studying the monomer composition, monomer ratio, molecular weight, etc. in the polyester resin. Specifically, by focusing on the polarity and composition distribution in the polyester resin structure, for example, a highly polar portion such as the structure represented by formula (A) contained in the carboxylic acid portion at the end of the polyester resin is unevenly distributed on the surface of the toner particles, and by controlling it by utilizing the difference in bulk between portions with different composition distributions as described below, it has become possible to control the orientation state of the structure represented by formula (A) for the first time. As a result, a toner having excellent low-temperature fixing properties and capable of realizing energy saving, high speed, and high image quality has been obtained.
[0019] In the toner of the present disclosure, when the amount of ions is measured from the surface of the toner particles to a depth of 100 nm by time-of-flight secondary ion mass spectrometry (TOF-SIMS) and the amount of ions counted having the structure represented by the following formula (A) is divided by the total amount of ions counted to obtain a standard value, one or more peaks of the standard value are present within a range of 100 nm from the surface of the toner particles. This is a prerequisite for controlling the presence state of the structure represented by formula (A) near the surface within the range of the present disclosure, and indicates that the toner particles of the present disclosure have the polyester resin within 100 nm from the surface of the toner particles. The number of peaks of the standard value is preferably 1 to 2, and more preferably 1.
[0020] [ka]
[0021] Time-of-flight secondary ion mass spectrometry, the details of which will be described later, can detect elements and molecular species near the surface of a sample with high sensitivity. The structure shown in formula (A) is a part of the molecular structure contained mainly in the ester bond site and the terminal carboxylic acid site of the polyester resin.
[0022] Furthermore, when the amount of ions is measured from the surface of a toner particle to a depth of 100 nm by TOF-SIMS, one or more peaks having normalized values are present, and the normalized value of the peak having the maximum normalized value among the one or more peaks is defined as A(dmax), and the normalized value at the surface of the toner particle is defined as A(0), then A(dmax) and A(0) satisfy the following formulas (1) and (2). 1.15≦A(dmax) / A(0)≦5.00 (1) 0.010≦A(0) (2)
[0023] Formula (1) expresses that the structure represented by formula (A) is unevenly distributed in a region deeper than the surface of the toner particle and within 100 nm from the surface of the toner particle. By satisfying formula (1), it is possible to improve the adhesion between toner particles when the toner is fixed. It is believed that this is because when the toner surface in which the structure represented by formula (A) is unevenly distributed is subjected to heat and pressure during the fixing process, the uneven distribution state is rapidly transformed into a uniform state, which promotes the deformation of the toner, leading to improved adhesion between toner particles.
[0024] Equation (2) indicates that the amount of the structure represented by formula (A) on the surface of the toner particle (i.e., 0 nm depth from the surface of the toner particle) is above a certain level. By simultaneously satisfying equations (1) and (2), the adhesion between the toner and the media, paper, can be improved. This is due to the promotion of the toner deformation mentioned above, as well as the high affinity between cellulose, the main component of paper, and the structure represented by formula (A). It is believed that the presence of the structure represented by formula (A) on the outermost surface of the toner particle above a certain level accelerates the speed at which the toner spreads onto the paper near the toner surface when it melts, leading to improved adhesion between the toner and paper.
[0025] In formula (1), when A(dmax) / A(0) is 1.15 or more, the adhesion between toner particles is sufficient. When A(dmax) / A(0) is 5.00 or less, the orientation of the structure represented by formula (A) can be controlled without using or combining polyester resins with extremely high or low physical properties such as molecular weight and acid value, and the structure represented by formula (A), i.e., polyester resin, is excessively unevenly distributed in the toner, causing the charge distribution on the surface of the toner particles to become broad, thereby suppressing adverse effects such as uneven density after fixing due to toner scattering. A(dmax) / A(0) is preferably 1.20 to 5.00, and more preferably A(dmax) and A(0) can be controlled by selecting the type and amount of monomers so that the polyester resin has a specific composition distribution.
[0026] Furthermore, when A(0) in formula (2) is 0.010 or more, the effect of improving the adhesion between the toner and paper can be sufficiently obtained. However, in a toner that contains a polyester resin within 100 nm from the surface of the toner particle, a certain amount of the structure represented by formula (A) is always present at a depth of 0 nm from the surface of the toner particle, i.e., on the surface of the toner particle, so it is difficult to manufacture and control a toner with A(0) less than 0.010.
[0027] The present inventors speculate that the mechanism by which the structure represented by the above formula (A) can be unevenly distributed near the surface of the toner particles is as follows: By designing a polyester resin to have a specific composition distribution, taking into consideration the state of existence of structural formula (A) in the polyester resin, such as unevenly distributing non-polar groups and polar groups in the polyester resin molecule, it is possible to control the state of existence of the structure represented by formula (A) in the polyester resin. As a specific method, for example, in the vicinity of the surface of the toner particles, the orientation state of the carboxylic acid group at the end of the polymer in the polyester resin molecule is aligned, or a polymer having a composition with a significantly different polarity distribution is used in combination, so that an ester bond site with a different composition distribution can be present. Furthermore, for example, in resin particles containing a polyester resin containing a structure represented by formula (A), the structure represented by formula (A) (ester bond site) in the polyester resin can be more easily transferred to the surface of the toner particles by treating the resin particles with a certain pH or higher and heat in an aqueous medium, or modifying the surface of the resin particles in a dry powder state by heat or the like. In addition, it is considered that by using two or more polyester resins having different composition distributions in combination as the polyester resin containing the structure represented by formula (A), a difference in bulkiness occurs, and steric hindrance occurs between the two or more polyester resins in the vicinity of the outermost surface of the toner particles, so that the structure represented by formula (A) can be precisely unevenly distributed in a region within a depth of 100 nm from the surface of the toner particles, rather than on the outermost surface of the toner particles.
[0028] Hereinafter, a preferred embodiment, a preferred material configuration, and a preferred production method for the toner of the present disclosure will be described.
[0029] (toner) In order to control the structure represented by the formula (A) to the unevenly distributed state as described above, when the standard value at a depth of 100 nm from the surface of the toner particle is defined as A(100) among the standard values when the toner particle is analyzed by TOF-SIMS, it is preferable that the above A(dmax) and A(100) satisfy the following formula (3). 1.15≦A(dmax) / A(100)≦5.00 (3) Formula (3) indicates that the structure represented by formula (A) is unevenly distributed in a region shallower than a position 100 nm or less from the surface of the toner particle and within 100 nm from the surface of the toner particle. By satisfying formula (3), toner scattering can be further suppressed, and an image with less density unevenness can be obtained. A(dmax) / A(100) is more preferably 1.50 to 3.00. A(100) can be controlled by selecting the type and amount of monomer so that the polyester resin has a specific composition distribution, or by changing the amount of polyester resin added.
[0030] Moreover, it is preferable that the A(0) satisfies the following formula (4). 0.010≦A(0)≦0.100 (4) When A(0) is 0.010 or more, the effect of improving the adhesion between the toner and paper is more preferably exhibited, and when A(0) is 0.100 or less, the amount of the structure represented by formula (A) present on the surface of the toner particles is not excessive, so that the effect of promoting deformation of the toner is easily obtained. A(0) is more preferably 0.010 to 0.080.
[0031] It is preferable that the A(100) satisfies the following formula (5). 0.010≦A(100)≦0.100 (5) By satisfying formula (5), it is easy to control the state of the structure represented by formula (A) within 100 nm from the surface of the toner particles, and when the toner particles have a core-shell structure, it is easy to control the shell thickness to 100 nm to 200 nm. A(100) is more preferably 0.010 to 0.080.
[0032] The softening point of the toner determined by a constant load extrusion type capillary rheometer is 150°C or less. The constant load extrusion type capillary rheometer can observe the melting property of a compression-formed sample against heat, although the details of the measurement method will be described later. The softening point is an index of the melting property, and it is considered that the lower the softening point, the easier it is for the toner to melt at a lower temperature. In order to obtain low-temperature fixability, it is necessary that the structure represented by formula (A) unevenly distributed near the surface of the toner particles is easily moved by melting the surface vicinity of the toner particles, and sufficient melting property is obtained when the softening point is 150°C or less. The softening point is preferably 140°C or less, more preferably 130°C or less. The lower limit of the softening point is not particularly limited, but can be, for example, 100°C or more. The softening point can be controlled by the composition design of the polyester resin or binder resin and the amount of the crystalline material.
[0033] (polyester resin) The toner contains toner particles having a polyester resin. The polyester resin may be used as a binder resin described later, or may be used as a component other than the binder resin. In addition, when the toner particles have a core-shell structure described later, the shell may contain the polyester resin, or the core may contain the polyester resin.
[0034] The content of the polyester resin in the toner particles is preferably 1.0% by mass to 95.0% by mass. When the toner particles contain a binder resin described below in addition to the polyester resin, the content of the polyester resin in the toner particles is more preferably 1.0% by mass to 30.0% by mass. When the toner particles contain the polyester resin as a binder resin, the content of the polyester resin in the toner particles is more preferably 50.0% by mass to 95.0% by mass.
[0035] The polyester resin is not particularly limited, and any known polyester resin can be used, but it is preferably an amorphous polyester resin. The material composition of the polyester resin is not particularly limited, and known materials can be used. Examples of the monomer include a dihydric alcohol monomer component and a dihydric acid monomer component. Examples of the divalent acid monomer component include the following dicarboxylic acids or derivatives thereof: benzene dicarboxylic acids such as phthalic acid, terephthalic acid, isophthalic acid, and phthalic anhydride, or their anhydrides, or their lower alkyl esters; alkyl dicarboxylic acids such as succinic acid, adipic acid, sebacic acid, and azelaic acid, or their anhydrides, or their lower alkyl esters; alkenyl succinic acids or alkyl succinic acids such as n-dodecenyl succinic acid and n-dodecyl succinic acid, or their anhydrides, or their lower alkyl esters; unsaturated dicarboxylic acids such as fumaric acid, maleic acid, citraconic acid, and itaconic acid, or their anhydrides, or their lower alkyl esters. The divalent acid monomer component can be used alone or in combination of two or more. Examples of the dihydric alcohol monomer component include the following: ethylene glycol, polyethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,6-hexanediol, neopentyl glycol, 1,4-cyclohexanediol, Methanol (CHDM), isosorbide, hydrogenated bisphenol A, bisphenol and its derivatives. The dihydric alcohol monomer component can be used alone or in combination of two or more.
[0036] The polyester resin may contain, in addition to the above-mentioned divalent acid monomer component and divalent alcohol monomer component, acid monomer components such as monovalent carboxylic acid compounds and trivalent or higher carboxylic acid compounds, and alcohol monomer components such as monovalent alcohol compounds and trivalent or higher alcohol compounds as constituent components. Examples of the monovalent carboxylic acid compound include aromatic carboxylic acids having 30 or less carbon atoms, such as benzoic acid and p-methylbenzoic acid, and aliphatic carboxylic acids having 30 or less carbon atoms, such as stearic acid and behenic acid. Examples of the monohydric alcohol compound include aromatic alcohols having 30 or less carbon atoms, such as benzyl alcohol, and aliphatic alcohols having 30 or less carbon atoms, such as lauryl alcohol, cetyl alcohol, stearyl alcohol, and behenyl alcohol. The trivalent or higher carboxylic acid compound is not particularly limited, but examples thereof include trimellitic acid, trimellitic anhydride, and pyromellitic acid. Examples of the trihydric or higher alcohol compounds include trimethylolpropane, pentaerythritol, and glycerin. The above-mentioned acid monomer components and alcohol monomer components can be used alone or in combination of two or more.
[0037] The content ratio of the monomer unit represented by the following formula (B) in the polyester resin is 30.0 mass% or more and 50.0 mass% or less (more preferably 40.0 mass% to 50.0 mass%) relative to the mass of the polyester resin, The content ratio of the monomer unit represented by the following formula (C) in the polyester resin is 25.0 mass% or more and 50.0 mass% or less (more preferably 25.0 mass% to 40.0 mass%) relative to the mass of the polyester resin, The content ratio of the monomer unit represented by the following formula (D) in the polyester resin is preferably 1.0 mass % or more and 50.0 mass % or less (more preferably 20.0 mass % to 30.0 mass %) relative to the mass of the polyester resin.
[0038] [ka] (In formula (B), R 1 indicates a benzene ring.)
[0039] [ka] (In formula (C), R 2represents an ethylene group or a propylene group, x and y are each an integer of 1 or more, and the average value of x+y in the polyester resin is 2 to 10.
[0040] [ka] (In formula (D), R 3 represents an ethylene group or a propylene group.
[0041] The dielectric tangent value of the polyester resin at 25°C and 10000Hz is preferably 0.0070 or more and 0.0140 or less. The dielectric tangent value can be controlled by changing the material composition of the polyester resin, but can be preferably controlled by including a monomer unit represented by the following formula (E) in the polyester resin. That is, the polyester resin preferably includes a monomer unit represented by the following formula (E), and the content ratio of the monomer unit represented by the following formula (E) in the polyester resin is more preferably 1.0 mass% or more and 5.0 mass% or less (more preferably 2.0 mass% to 4.0 mass%) relative to the mass of the polyester resin.
[0042] [ka]
[0043] Furthermore, when acetonitrile is used as a poor solvent and chloroform is used as a good solvent for the chloroform-soluble portion of the polyester resin, and the mobile phase composition is changed linearly from 100% by mass acetonitrile to 100% by mass chloroform, and the eluted components are analyzed by gradient polymer elution chromatography, two or more peaks are obtained, and the normalized value of the maximum peak among the two or more peaks (the normalized value of the peak showing the maximum peak intensity) is S(1), and the normalized value of the second maximum peak (the normalized value of the peak showing the second maximum peak intensity) is S(2), it is preferable that S(1) and S(2) satisfy the following formula (6). 0.40≦S(2) / S(1)<1.00 (6)
[0044] Although the detailed measurement method will be described later, gradient polymer elution chromatography (GPEC) analysis is an analytical method that can separate polar polymers using a column based on the difference in polarity. Formula (6) indicates that the polyester resin has moieties with different polarities, that is, that it has a composition distribution. The presence of a composition distribution makes it easier to unevenly distribute the structure represented by formula (A) contained in the polyester resin in the toner. In the GPEC measurement, the more polarity is separated, the more distant the peaks appear. Therefore, two or more peaks may overlap, but it is preferable that the peak having S(1) and the peak having S(2) are independent. In other words, it is preferable that the polar part and the non-polar part of the polyester resin exist while maintaining a certain distance. By unevenly distributing the polar part and the non-polar part in this way, the structure represented by formula (A) is likely to be unevenly distributed in the polyester resin. If S(2) / S(1) is 0.40 or more, the peak having S(1) and the peak having S(2) are likely to appear independently. It is more preferable that S(2) / S(1) is 0.50 to 0.80. S(2) / S(1) can be controlled by changing the composition of the monomers constituting the polyester resin.
[0045] The polyester resin has a weight average molecular weight (Mw) of preferably 9000 to 15000, and more preferably 10000 to 13000. The polyester resin has an acid value of preferably 4.0 mgKOH / g to 10.0 mgKOH / g, and more preferably 4.5 mgKOH / g to 8.0 mgKOH / g.
[0046] The method for producing the polyester resin is not particularly limited, and any known method can be used.
[0047] (Binding resin) The toner particles preferably contain a binder resin. The content of the binder resin in the toner particles is preferably 50.0% by mass to 95.0% by mass. The binder resin is not particularly limited, and the polyester resin of the present disclosure can be used as the binder resin. In addition, the following resins can also be used as the binder resin. Vinyl resins using polymerizable monomers, polyester resins other than the polyester resins of the present disclosure, polyol resins, polyvinyl chloride resins, phenolic resins, natural resin modified phenolic resins, natural resin modified maleic acid resins, acrylic resins, methacrylic resins, polyvinyl acetate, silicone resins, polyurethane resins, polyamide resins, furan resins, epoxy resins, xylene resins, polyvinyl butyral, terpene resins, coumarone-indene resins, and petroleum-based resins. Preferred are vinyl resins such as styrene-acrylic resins, polyester resins (including both the polyester resins of the present disclosure and polyester resins other than the polyester resins of the present disclosure), mixtures of polyester resins and vinyl resins, or hybrid resins in which both are partially reacted, and more preferred are styrene-acrylic resins and the polyester resins of the present disclosure. These binder resins can be used alone or in combination of two or more.
[0048] (Polymerizable monomer) As the polymerizable monomer capable of producing the binder resin, for example, a vinyl monomer capable of radical polymerization is used. As the vinyl monomer, a monofunctional monomer or a polyfunctional monomer can be used. Examples of monofunctional monomers include styrene; styrene derivatives such as α-methylstyrene, β-methylstyrene, ο-methylstyrene, m-methylstyrene, p-methylstyrene, p-methoxystyrene, and p-phenylstyrene; acrylic polymerizable monomers such as methyl acrylate, ethyl acrylate, n-propyl acrylate, iso-propyl acrylate, n-butyl acrylate, dibutyl phosphate ethyl acrylate, and 2-benzoyloxyethyl acrylate; methacrylic polymerizable monomers such as methyl methacrylate, ethyl methacrylate, and dibutyl phosphate ethyl methacrylate; methylene aliphatic monocarboxylic acid esters; vinyl esters such as vinyl acetate and vinyl propionate; vinyl ethers such as vinyl methyl ether, vinyl ethyl ether, and vinyl isobutyl ether; and vinyl ketones such as vinyl methyl ketone, vinyl hexyl ketone, and vinyl isopropyl ketone. Examples of the polyfunctional monomer include diethylene glycol diacrylate, triethylene glycol diacrylate, tetraethylene glycol diacrylate, polyethylene glycol diacrylate, tetramethylolmethane tetramethacrylate, divinylbenzene, and divinyl ether. Among the above, the polymerizable monomer preferably includes styrene or a styrene derivative and an acrylic polymerizable monomer. These polymerizable monomers may be used alone or in combination of two or more.
[0049] A crosslinking agent can also be used for the polymerizable monomer. Specifically, compounds having two or more polymerizable double bonds, such as those exemplified below, are used. Carboxylic acid esters having two double bonds, such as propylene glycol diacrylate, ethylene glycol diacrylate, 1,6-hexanediol diacrylate, and 1,3-butanediol dimethacrylate, aromatic divinyl compounds such as divinylbenzene and divinylnaphthalene, divinyl compounds such as divinylaniline, divinyl ether, divinyl sulfide, and divinyl sulfone, and compounds having three or more vinyl groups. From the viewpoint of achieving both low-temperature fixability and high-temperature elasticity, it is preferable to use a carboxylic acid ester. These crosslinking agents can be used alone or in combination of two or more. The amount of the crosslinking agent added is preferably 0.01 parts by mass or more and 5.00 parts by mass or less, and more preferably 0.10 parts by mass or more and 3.00 parts by mass or less, based on 100 parts by mass of the polymerizable monomer that forms the binder resin or the binder resin.
[0050] A polymerization initiator may be used when producing toner particles. As the polymerization initiator, a hydrophobic initiator and a water-soluble initiator are used. Preferably, the initiator has a half-life of 0.5 to 30 hours at the reaction temperature during the polymerization reaction. In addition, when the polymerization reaction is carried out with an addition amount of 0.5 to 20 parts by mass per 100 parts by mass of the polymerizable monomer, a polymer having a maximum molecular weight between 10,000 and 100,000 can be obtained, which is preferable because it is possible to obtain toner particles having appropriate strength and melting properties. Examples of the polymerization initiator include azo or diazo polymerization initiators such as 2,2'-azobis-(2,4-dimethylvaleronitrile), 2,2'-azobisisobutyronitrile, 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis-4-methoxy-2,4-dimethylvaleronitrile, and azobisisobutyronitrile; and peroxide polymerization initiators such as benzoyl peroxide, t-butyl peroxy 2-ethylhexanoate, t-butyl peroxy pivalate, t-butyl peroxy isobutyrate, t-butyl peroxy neodecanoate, methyl ethyl ketone peroxide, diisopropyl peroxycarbonate, cumene hydroperoxide, 2,4-dichlorobenzoyl peroxide, and lauroyl peroxide. These polymerization initiators can be used alone or in combination of two or more. In order to control the degree of polymerization of the polymerizable monomer, it is also possible to further add and use a known chain transfer agent, polymerization inhibitor, etc.
[0051] (core-shell structure) The toner particles preferably have a core and a shell covering the core, i.e., have a core-shell structure. The core preferably contains a styrene-acrylic resin. The shell preferably contains the polyester resin of the present disclosure. When the toner particles have a core-shell structure having a core containing a styrene-acrylic resin and a shell covering the core and containing the polyester resin of the present disclosure, it is easier to control the orientation state of the structure represented by formula (A) of the polyester resin in the vicinity of the surface of the toner particles. When the toner has toner particles having the core-shell structure, the content of the polyester resin of the present disclosure is preferably 1.0 parts by mass or more and 10.0 parts by mass or less, and more preferably 5.00 parts by mass or more and 10.0 parts by mass or less, relative to 100 parts by mass of the styrene-acrylic resin. In addition, in the cross section of the toner observed with a transmission electron microscope, the shell thickness is preferably 100 nm or more and 200 nm or less, and more preferably 100 nm or more and 150 nm or less. The shell thickness can be controlled by the composition of the monomer constituting the polyester resin and the content of the polyester resin.
[0052] (crystalline material) The toner particles preferably contain a crystalline material, and when the toner particles have a core-shell structure, the core preferably contains a crystalline material. When the toner particles have the crystalline material, the content of the crystalline material is preferably 5.00 parts by mass or more and 50 parts by mass or less, and more preferably 5.00 parts by mass or more and 10.0 parts by mass or less, relative to 100 parts by mass of the styrene-acrylic resin. The crystalline material is not particularly limited, and any known material having crystallinity can be used. Here, "having crystallinity" means that the material exhibits a clear melting point in measurement using a differential scanning calorimeter (DSC). From the viewpoint of low-temperature fixing property and releasability, it is preferable to use at least one selected from the group consisting of ester wax, hydrocarbon wax, and crystalline polyester resin as the crystalline material. The ester wax is a wax containing fatty acid ester as a main component.
[0053] Preferred ester waxes are described below. The functionality described below indicates the number of ester groups contained in one molecule. For example, behenyl behenate is a monofunctional ester wax, and dipentaerythritol hexabehenate is a hexafunctional ester wax. The monofunctional ester wax is preferably a condensate of an aliphatic alcohol and an aliphatic carboxylic acid, in which the aliphatic alcohol preferably has 6 to 26 carbon atoms, and the aliphatic carboxylic acid preferably has 6 to 26 carbon atoms. Examples of aliphatic alcohols include 1-hexanol, 1-heptanol, 1-octanol, 1-nonanol, 1-decanol, undecyl alcohol, lauryl alcohol, behenyl alcohol, and stearyl alcohol. Examples of aliphatic carboxylic acids include pentanoic acid, hexanoic acid, heptanoic acid, octanoic acid, nonanoic acid, decanoic acid, behenic acid, and stearic acid. As the bifunctional ester wax, for example, a combination of a dicarboxylic acid and a monoalcohol, or a diol and a monocarboxylic acid can be used. Examples of dicarboxylic acids include adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, and dodecanedioic acid. Examples of diols include 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, and 1,12-dodecanediol. The monoalcohol to be condensed with the dicarboxylic acid is preferably an aliphatic alcohol.Specific examples thereof include tetradecanol, pentadecanol, hexadecanol, heptadecanol, octadecanol, nonadecanol, eicosanol, docosanol, tricosanol, tetracosanol, pentacosanol, hexacosanol, and octacosanol.Of these, docosanol is preferred from the viewpoint of fixing property and developing property. The monocarboxylic acid to be condensed with the diol is preferably an aliphatic carboxylic acid. Specific examples include lauric acid, myristic acid, palmitic acid, margaric acid, stearic acid, tuberculostearic acid, arachidic acid, behenic acid, lignoceric acid, and cerotic acid. Among them, behenic acid is preferable from the viewpoint of fixing property and developing property. Although linear fatty acids and linear alcohols are exemplified here, fatty acids having a branched structure and alcohols having a branched structure may also be used. These ester waxes can be used alone or in combination of two or more.
[0054] The crystalline polyester resin as a crystalline material will be described below. The crystalline polyester resin is not particularly limited and any known resin may be used, but it is preferably a saturated polyester. Further, the crystalline polyester resin is preferably a condensation product of at least one selected from the group consisting of an aliphatic monocarboxylic acid and an aliphatic monoalcohol, an aliphatic dicarboxylic acid, and an aliphatic diol. More preferably, and an aliphatic monocarboxylic acid condensate. By incorporating at least one selected from the group consisting of an aliphatic monocarboxylic acid and an aliphatic monoalcohol as a constituent of the crystalline polyester resin, it becomes easier to adjust the molecular weight and hydroxyl value of the crystalline polyester resin.
[0055] Examples of monomers that can be used for the crystalline polyester resin as the crystalline material are given below. Examples of the aliphatic dicarboxylic acid include oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, dodecanedioic acid, hexadecanedicarboxylic acid, and octadecanedicarboxylic acid. Examples of aliphatic diols include ethylene glycol, diethylene glycol, triethylene glycol, 1,2-propanediol, 1,3-propanediol, dipropylene glycol, trimethylene glycol, neopentyl glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,16-hexadecanediol, and 1,18-octadecanediol. Examples of aliphatic monocarboxylic acids include decanoic acid (capric acid), dodecanoic acid (lauric acid), tetradecanoic acid (myristic acid), hexadecanoic acid (palmitic acid), octadecanoic acid (stearic acid), eicosanoic acid (arachidic acid), docosanoic acid (behenic acid), and tetracosanoic acid (lignoceric acid). Examples of the aliphatic monoalcohol include lauryl alcohol, stearyl alcohol, and behenyl alcohol. By using such a monocarboxylic acid and monoalcohol, a crystalline polyester resin having an alkyl group (preferably an alkyl group having 2 to 24 carbon atoms) at the terminal can be obtained. Here, since the monocarboxylic acid has one carboxylic acid, the structure derived from the monocarboxylic acid is located at the end of the molecular chain of the crystalline polyester resin. These monomers can be used alone or in combination of two or more.
[0056] The method for producing the crystalline polyester resin is not particularly limited, and it can be produced by a conventional polyester synthesis method. For example, the crystalline polyester resin can be obtained by esterifying or transesterifying a dicarboxylic acid component and a diol component, and then polycondensing the diol component under reduced pressure or by introducing nitrogen gas according to a conventional method.
[0057] The hydrocarbon wax is an aliphatic hydrocarbon wax, such as low molecular weight polyethylene, low molecular weight polypropylene, microcrystalline wax, Fischer-Tropsch wax, paraffin wax, polyolefin wax, etc. These hydrocarbon waxes can be used alone or in combination of two or more.
[0058] When the core of a toner particle contains a crystalline material, in a cross section of the toner observed with a transmission electron microscope, The average number of domains of the crystalline material is 8 to 500 (more preferably 250 to 500); The number average of the major axis of the domains of the crystalline material is 50 nm or more and 300 nm or less (more preferably 100 nm to 200 nm); The ratio of the domains present in an area of 25% or less of the distance from the outline of the cross section to the geometric center of the cross section (hereinafter, the ratio is also referred to as "25% ratio") is 60% by number or more and 100% by number or less (more preferably 80% by number to 95% by number) with respect to the total number of domains present in the cross section. By controlling the domain of the crystalline material as described above, it is possible to prevent the formation of a crystal during any time other than the fixing step. This is advantageous from the viewpoints of suppressing bleeding due to fixation of the crystalline material and uniform melting of the toner during fixing, and can further improve low-temperature fixing properties. The average number of domains of the crystalline material and the number-average diameter of the major axis of the domains of the crystalline material can be controlled by the cooling rate in the cooling step described below and the amount of crystalline material added. Furthermore, the above 25% ratio can be controlled by appropriately setting the difference between the cooling start temperature and the cooling end temperature in addition to the cooling rate and the amount of crystalline material added in the cooling step.
[0059] (Coloring agent) The toner particles may contain a colorant. As the black colorant, for example, a magnetic material or carbon black can be used, and a toner toned to black using a yellow colorant, a magenta colorant, and a cyan colorant described below can also be used. Examples of yellow colorants include compounds such as condensed azo compounds, isoindolinone compounds, anthraquinone compounds, azo metal complexes, methine compounds, and allylamide compounds.Specific examples include CI Pigment Yellow 12, 13, 14, 15, 17, 62, 73, 74, 83, 93, 94, 95, 97, 109, 110, 111, 120, 128, 129, 138, 147, 150, 151, 154, 155, 168, 180, 185, and 214. Examples of magenta colorants include condensed azo compounds, diketopyrrolopyrrole compounds, anthraquinone compounds, quinacridone compounds, basic dye lake compounds, naphthol compounds, benzimidazolone compounds, thioindigo compounds, and perylene compounds.Specific examples of the magenta colorant include CI Pigment Red 2, 3, 5, 6, 7, 23, 48:2, 48:3, 48:4, 57:1, 81:1, 122, 146, 166, 169, 177, 184, 185, 202, 206, 220, 221, 238, 254, 269, and CI Pigment Violet 19. Examples of cyan colorants include copper phthalocyanine compounds and their derivatives, anthraquinone compounds, and basic dye lake compounds. Specific examples include CI Pigment Blue 1, 7, 15, 15:1, 15:2, 15:3, 15:4, 60, 62, and 66. These colorants can be used alone or in a mixture of two or more, and can also be used in the form of a solid solution. The colorant is selected in terms of hue angle, chroma, brightness, light resistance, OHP transparency, and dispersibility in the toner. The content of the colorant is preferably 1 part by mass or more and 100 parts by mass or less per 100 parts by mass of the polymerizable monomer capable of forming the binder resin or the binder resin.
[0060] The toner may be a magnetic toner in which a magnetic material is contained in the toner particles as a colorant. The magnetic material is mainly composed of magnetic iron oxide such as triiron tetroxide or γ-iron oxide, and may also contain elements such as phosphorus, cobalt, nickel, copper, magnesium, manganese, aluminum, and silicon. These magnetic materials have a BET specific surface area of 2 m by nitrogen adsorption method. 2 / g~30m 2 / g, and 3m 2 / g~28m 2 / g. Also, the Mohs hardness is preferably 5 to 7. The shape of the magnetic material may be polyhedral, octahedral, hexahedral, spherical, needle-like, or scaly, and the like, with polyhedral, octahedral, hexahedral, spherical, or other shapes having little anisotropy being preferred in terms of increasing image density.
[0061] The magnetic material preferably has a number-average particle size of 0.10 μm to 0.40 μm. In general, the smaller the particle size of the magnetic material, the higher the coloring power but the more likely the magnetic material is to aggregate, so the above range is preferable from the viewpoint of the balance between coloring power and aggregation properties. The number-average particle size of the magnetic material can be measured using a transmission electron microscope. Specifically, the toner particles to be observed are thoroughly dispersed in an epoxy resin, and then the resin is cured for two days in an atmosphere at a temperature of 40°C to obtain a cured product. The cured product is cut into thin slice samples using a microtome, and the slices are then examined under a transmission electron microscope (TEM) at a magnification of 10,000 to 40,000 times. The diameters of 100 magnetic particles in the field of view are measured using a photograph. The number-average particle size is then calculated based on the equivalent diameter of a circle equal to the projected area of the magnetic particles. It is also possible to measure particle size using an image analyzer.
[0062] The magnetic material can be produced, for example, by the following method. An alkali such as sodium hydroxide is added to an aqueous solution of a ferrous salt in an amount equivalent or greater to the iron component to prepare an aqueous solution containing ferrous hydroxide. Air is blown into the aqueous solution while maintaining the pH of the prepared solution at pH 7 or higher, and the aqueous solution is heated to 70°C or higher to carry out an oxidation reaction of the ferrous hydroxide, thereby first producing seed crystals that will become the cores of the magnetic iron oxide powder. Next, an aqueous solution containing about 1 equivalent of ferrous sulfate is added to the slurry liquid containing the seed crystals based on the amount of alkali added previously. The reaction of ferrous hydroxide is allowed to proceed while air is blown in while maintaining the pH of the liquid at 5 to 10, and magnetic iron oxide powder is grown around the seed crystals as a core. At this time, the shape and magnetic properties of the magnetic material can be controlled by selecting any pH, reaction temperature, and stirring conditions. As the oxidation reaction progresses, the pH of the liquid shifts to the acidic side, but it is preferable not to make the pH of the liquid less than 5. The magnetic material thus obtained can be obtained by filtering, washing, and drying it by a standard method.
[0063] In addition, when the toner is produced in an aqueous medium, the magnetic material surface may be subjected to a hydrophobic treatment. The method of hydrophobic treatment is not particularly limited, and may be either a dry method or a wet method. When the surface treatment is performed by a dry method, the magnetic material that has been washed, filtered, and dried may be treated with a coupling agent. When the surface treatment is performed by a wet method, the dried material may be redispersed after the oxidation reaction is completed, or the iron oxide obtained by washing and filtering after the oxidation reaction is completed may be redispersed in another aqueous medium without drying, and then the coupling treatment may be performed.
[0064] Coupling agents that can be used in the surface treatment of the magnetic material include, for example, silane coupling agents, titanium coupling agents, etc. Silane coupling agents are more preferably used, for example, those represented by the following formula (7). R m SiY n (7) In the formula, R represents an alkoxy group, m represents an integer of 1 to 3, Y represents a functional group such as an alkyl group, a vinyl group, an epoxy group, or a (meth)acrylic group, and n represents an integer of 1 to 3, provided that m+n=4. In the formula (7), Y is preferably an alkyl group. More preferably, Y is an alkyl group having 3 to 16 carbon atoms, and particularly preferably, Y is an alkyl group having 3 to 10 carbon atoms. When the above-mentioned silane coupling agents are used, they can be used alone or in combination of two or more kinds. When two or more kinds are used in combination, the treatment can be performed with each coupling agent individually or simultaneously. The total amount of the coupling agent used is preferably 0.9 parts by mass or more and 3.0 parts by mass or less per 100 parts by mass of the magnetic material, and the amount of the treatment agent can be adjusted depending on the surface area of the magnetic material, the reactivity of the coupling agent, etc.
[0065] In addition to the above-mentioned materials, the toner particles may contain known functional resins, charge control agents, conductivity imparting agents, lubricants, abrasives, and the like.
[0066] (Toner manufacturing method) The method for producing the toner particles may be any of the known methods such as a dry method, an emulsion polymerization method, a solution suspension method, a suspension polymerization method, etc. In order to control the state of the structure represented by formula (A) near the surface of the toner particles within the range of the present disclosure, it is preferable to have the following steps. A step of obtaining resin particles containing a polyester resin; a dispersing step of dispersing the obtained resin particles in an aqueous medium to obtain a suspension; A treatment step of treating the above at pH (1) at 95° C. or higher and then treating the above at pH (2); A cooling step of cooling the suspension treated in the treatment step at a cooling rate of 50° C. / min or more, A process for treating so that pH(1) and pH(2) satisfy the following formulas (10) and (11). (Hereinafter, the process for treating so as to satisfy these requirements will be referred to as a "high-temperature, high-pH treatment process.") pH(1) <pH(2) (10) 6.0≦pH(2)≦10.5 (11)
[0067] It is believed that this high-temperature, high-pH treatment process orients the carboxylic acid at the end of the polyester resin toward the surface of the toner particles, and allows the ester bond site to be unevenly distributed near the surface of the toner particles. Therefore, the orientation state of the structure represented by formula (A) can be controlled more precisely, and it is easy to unevenly distribute it to a depth of 100 nm or less from the surface of the toner particles. In addition, the material selectivity of polyester resins and the like is improved.
[0068] By carrying out the treatment within the above pH range under conditions of a higher temperature than usual, such as 95°C or higher (more preferably 95°C to 100°C), the orientation state of the molecules in the polyester resin can be easily changed. In formula (10), by making pH(2) higher than pH(1), the orientation state of the polyester resin fixed in the obtained resin particles can be easily changed. Specifically, by making pH(2) 6.0 or more in formula (11), the carboxylic acid at the end of the polyester resin is easily dissociated by acid, so that the carboxylic acid at the end of the polyester resin is easily directed selectively toward the surface side of the toner particles, and the orientation state is easily controlled more precisely. Furthermore, by making pH(2) 10.5 or less, the generation of bubbles that tend to cause the generation of coarse particles is suppressed, and the generation of fogging due to poor charging caused by the generated coarse particles can be suppressed. pH(2) is more preferably 7.0 to 9.0. Furthermore, pH(1) is more preferably 3.0 or more and less than 6.0.
[0069] When toner particles are produced in an aqueous medium by a suspension polymerization method, an emulsion aggregation method, or the like, a suspension in which resin particles are dispersed in an aqueous medium is obtained, and it is preferable to carry out the high-temperature, high-pH treatment using the suspension. When toner particles are produced by a dry method, such as a pulverization method, it is preferable to carry out the high-temperature, high-pH treatment step after reslurrying the obtained resin particles in an aqueous medium to obtain a suspension. When the high-temperature, high-pH treatment step is not carried out, it is preferable to carry out a surface modification step for the resin particles as described below.
[0070] In the present disclosure, it is preferable to produce toner particles by a suspension polymerization method in which a polymerizable monomer composition is granulated in an aqueous medium to form particles of the polymerizable monomer composition. In the method for producing toner particles by a suspension polymerization method, as a process for obtaining resin particles containing a polyester resin, the method can include a granulation process for forming particles of a polymerizable composition containing a polymerizable monomer and a polyester resin in an aqueous medium, and a polymerization process for obtaining resin particles by polymerizing the polymerizable monomer contained in the particles of the polymerizable composition. After the polymerization step, the high temperature and high pH treatment step is preferably carried out. Furthermore, after the high temperature and high pH treatment, it is preferable to have a process for obtaining toner particles having a desired particle size through a cooling process for controlling the location and size of the domains of the crystalline material and a holding (annealing) process for controlling the crystallinity of the crystalline material.
[0071] In order to control the location and size of the domains of the crystalline material, the toner manufacturing method preferably includes a cooling step for cooling the suspension. It is also preferable to include a holding (annealing) step for controlling the crystallinity of the crystalline material. Among these, it is more preferable to increase the cooling rate until the suspension that has been subjected to the high-temperature, high-pH treatment step is cooled to the temperature after cooling. Specifically, the cooling rate is preferably 50° C. / min or more, and more preferably 50° C. / min or more. The cooling rate is more preferably at most 350° C. / min, and even more preferably at least 100° C. / min but no greater than 300° C. / min. The cooling start temperature in the cooling step is also preferably at least 70° C. but no greater than 100° C.
[0072] It is also preferable that the annealing temperature in the annealing step is 40° C. or more and 65° C. or less. The holding time in the annealing step is not particularly limited, but can be 1 hour to 10 hours.
[0073] The resin particles thus obtained are filtered, washed, and dried by a known method to obtain toner particles. The toner particles can be used as they are as a toner, but if necessary, inorganic particles as a flowability improver can be mixed and attached to the surface of the toner particles to obtain a toner.
[0074] The inorganic particles may be any known type. Preferably, the inorganic particles are titania particles, silica particles such as wet-process silica, dry-process silica, or inorganic particles obtained by surface-treating the silica particles with a silane coupling agent, a titanium coupling agent, silicone oil, or the like. The inorganic particles that have been surface-treated preferably have a hydrophobicity of 30 or more and 98 or less as determined by a methanol titration test.
[0075] An example of a method for producing toner particles by a pulverization method will be described in detail below. In the raw material mixing step, the materials constituting the toner particles, such as polyester resin, and optionally binder resin, colorant, and other additives, can be weighed out in predetermined amounts, blended, and mixed. Examples of mixing devices include a double cone mixer, a V-type mixer, a drum-type mixer, a super mixer, an FM mixer, a Nauta mixer, and a Mechano Hybrid (manufactured by Nippon Coke and Engineering Co., Ltd.).
[0076] Next, the mixed materials are melt-kneaded to disperse the colorant and the like to obtain a kneaded product. In the melt-kneading process, a batch kneader such as a pressure kneader or a Banbury mixer, or a continuous kneader can be used. A single-screw or twin-screw extruder is preferred because of its advantage of being able to produce continuously. Examples of single-screw or twin-screw extruders include a KTK type twin-screw extruder (manufactured by Kobe Steel, Ltd.), a TEM type twin-screw extruder (manufactured by Toshiba Machine Co., Ltd.), a PCM kneader (manufactured by Ikegai), a twin-screw extruder (manufactured by KCK Corporation), a Co-Kneader (manufactured by Buss Co., Ltd.), and a Kneadex (manufactured by Nippon Coke and Engineering Co., Ltd.). Furthermore, the kneaded product obtained by melt-kneading may be rolled with a two-roller or the like and cooled with water or the like in a cooling process.
[0077] The cooled mixture can then be pulverized to a desired particle size in a pulverizing process, which can be performed by, for example, coarse pulverization using a pulverizer such as a crusher, hammer mill, or feather mill, followed by further pulverization using, for example, a Cryptron System (Kawasaki Heavy Industries), a Super Rotor (Nisshin Engineering), a Turbo Mill (Freund Turbo), or an air jet type pulverizer.
[0078] Thereafter, if necessary, the mixture can be classified using a classifier or sieve such as an inertial classification type Elbow Jet (manufactured by Nippon Steel Mining Co., Ltd.), a centrifugal classification type Turboplex (manufactured by Hosokawa Micron Corporation), a TSP Separator (manufactured by Hosokawa Micron Corporation), or a Faculty (manufactured by Hosokawa Micron Corporation) to obtain resin particles.
[0079] Furthermore, it is preferable to reslurry the obtained resin particles in an aqueous medium to obtain a suspension, and then to carry out the above-mentioned high-temperature, high-pH treatment step. If the high-temperature, high-pH treatment step is not carried out, it is preferable to carry out surface modification, i.e., spheronization, of the obtained resin particles in a surface modification step. As the surface modification step, a thermal spheronization treatment using hot air is preferably used. As an apparatus that can be used for the surface modification treatment of resin particles using hot air, for example, a Surfusion System (Nihon New Surface modification may also be performed by heating resin particles in a surface modification device that applies a high-velocity airflow impact method, such as a Hybridization System (manufactured by Nara Machinery Works), a Cryptron Cosmo System (manufactured by Kawasaki Heavy Industries, Ltd.), or an Innomizer System (manufactured by Hosokawa Micron Corporation), or a surface modification device that applies a dry mechanochemical method, such as a Mechanofusion System (manufactured by Hosokawa Micron Corporation) or a Mechanomill (manufactured by Okada Seikosha Co., Ltd.).
[0080] Also, a surface modification device as shown in FIG. 5 can be used. Using an auto feeder 102, resin particles 101 are supplied through a supply nozzle 103 to an interior 104 of the surface modification device. Since the air in the interior 104 of the surface modification device is sucked in by a blower 109, the resin particles 101 introduced from the supply nozzle 103 are dispersed in the device. The resin particles 101 dispersed in the device are instantly heated by hot air introduced from a hot air inlet 105, and the surface is modified. The temperature of the introduced hot air can be adjusted to 100° C. or higher and 450° C. or lower, and the setting can be changed at any time according to the toner prescription. It is preferable to set the temperature of the hot air to 100° C. or higher from the viewpoint of uniformity of heat treatment and productivity. In addition, if the temperature of the hot air is set to 450° C. or lower, it is possible to suppress the size of the surface modification device itself and to easily adjust the thermal energy received by the resin particles during processing. In addition, it becomes possible to sufficiently control the temperature in the surface modification device, and it may be possible to suppress the occurrence of a fusion phenomenon.
[0081] In the apparatus of FIG. 5, hot air is generated by a heater, but the heater is not limited to the heater as long as it can generate hot air sufficient for surface modification of the resin particles. The surface-modified resin particles 107 may be instantly cooled by cold air introduced from the cold air inlet 106. In this case, dehumidified compressed air or N2 gas can be used as the cold air. In addition, from the viewpoint of forming an optimal temperature distribution in the apparatus by interaction with the airflow introduced into the apparatus other than the cold air, the temperature of the cold air is preferably -100°C or more and 60°C or less, more preferably -20°C or more and 20°C or less. When the temperature of the cold air is -100°C to 60°C, the case where excessive energy is required for the heat treatment is reduced, and the treatment itself tends to be uniform.
[0082] The resin particles may be spheroidized. For example, after pulverization, the resin particles may be spheroidized using a Hybridization System (manufactured by Nara Machinery Works), a Mechanofusion System (manufactured by Hosokawa Micron Corporation), a Faculty (manufactured by Hosokawa Micron Corporation), or a Meteor Rainbow MR Type (manufactured by Nippon Pneumatic Mfg. Co., Ltd.).
[0083] The obtained resin particles can be used as they are as toner particles, and the toner particles can be used as they are as they are, or the toner can be obtained by mixing inorganic particles as a flowability improver with the toner particles as necessary and attaching them to the surfaces of the toner particles. However, it is preferable to reslurry the obtained resin particles in an aqueous medium to obtain a suspension, and then perform the above-mentioned high-temperature high-pH treatment.
[0084] Thereafter, the mixture is filtered, washed, and dried by a known method, and if necessary, inorganic particles are mixed as a flowability improver and attached to the surface to obtain a toner. Known inorganic particles can be used. Preferred are titania particles, silica particles such as wet-processed silica and dry-processed silica, and inorganic particles obtained by subjecting such silica to a surface treatment with a silane coupling agent, a titanium coupling agent, silicone oil, or the like. The inorganic particles that have been subjected to the surface treatment preferably have a hydrophobicity of 30 or more and 98 or less as determined by a methanol titration test.
[0085] An example of a method for producing toner particles by the emulsion aggregation method will now be described in detail. (Polymer dispersion preparation process) The binder resin particle dispersion liquid is prepared, for example, as follows. In the case of a homopolymer or copolymer of a monomer (vinyl resin), a dispersion liquid in which vinyl resin particles are dispersed in an ionic surfactant can be prepared by carrying out emulsion polymerization or seed polymerization of a vinyl monomer in an ionic surfactant.
[0086] When the binder resin is a resin other than a vinyl resin such as a polyester resin, the resin is mixed with an aqueous medium in which an ionic surfactant or a polymer electrolyte is dissolved, and then the solution is heated to a temperature equal to or higher than the melting point or softening point of the resin to dissolve it, and a dispersion liquid in which the binder resin particles are dispersed in the ionic surfactant can be prepared using a dispersing machine with strong shear force such as a homogenizer. The dispersion means is not particularly limited, and examples thereof include known dispersion devices such as a rotary shear homogenizer, a ball mill having a media, a sand mill, and a dyno mill. A phase inversion emulsification method may also be used as a method for preparing a dispersion. The phase inversion emulsification method is a method in which a binder resin is dissolved in an organic solvent, a neutralizer and a dispersion stabilizer are added as necessary, and an aqueous solvent is dropped under stirring to obtain emulsified particles, and then the organic solvent in the resin dispersion is removed to obtain an emulsion. In this case, the order of adding the neutralizer and the dispersion stabilizer may be changed as appropriate.
[0087] In the emulsion aggregation method, a colorant particle dispersion may be used as necessary. The colorant particle dispersion is prepared by dispersing at least colorant particles in a dispersant. In the emulsion aggregation method, a wax particle dispersion may be used as necessary. The wax particle dispersion is prepared by dispersing at least wax particles in a dispersant.
[0088] (Agglutination process) The aggregation step of forming aggregated particles is a step of forming aggregated particles containing binder resin particles, and, if necessary, colorant particles, wax particles, etc., which are added as necessary, in an aqueous medium containing binder resin particles, and, if necessary, colorant particles, wax particles, etc.
[0089] (fusion process) The fusion process is a process in which the obtained aggregated particles are heated and fused. Before the fusion process, a pH adjuster, a polar surfactant, a non-polar surfactant, etc. may be appropriately added to prevent fusion between toner particles. The heating temperature may be at least the glass transition temperature of the resin contained in the aggregated particles (when there are two or more types of resin, the glass transition temperature of the resin having the highest glass transition temperature) and less than the decomposition temperature of the resin. Therefore, the heating temperature differs depending on the type of resin of the binder resin particles and cannot be generally specified, but is generally at least the glass transition temperature of the resin contained in the aggregated particles and less than 140°C. Heating can be performed using a heating device or tool known per se.
[0090] The fusion time is preferably short if the heating temperature is high, and long if the heating temperature is low. That is, the fusion time depends on the heating temperature and cannot be generally defined, but is generally 30 minutes or more and 10 hours or less. The resin particles are obtained by carrying out the above-mentioned dispersion liquid preparation step, aggregation step, and fusion step. The obtained resin particles can be directly subjected to subsequent steps such as filtration, washing, and drying by a known method to obtain toner particles, but it is preferable to carry out the above-mentioned high temperature and high pH treatment. Thereafter, the mixture is filtered, washed, and dried by a known method, and if necessary, inorganic particles are mixed as a flowability improver and attached to the surface to obtain a toner. Known inorganic particles can be used. Preferred are titania particles, silica particles such as wet-processed silica and dry-processed silica, and inorganic particles obtained by subjecting such silica to a surface treatment with a silane coupling agent, a titanium coupling agent, silicone oil, or the like. The inorganic particles that have been subjected to the surface treatment preferably have a hydrophobicity of 30 or more and 98 or less as determined by a methanol titration test.
[0091] <Measurement methods for various physical properties> Next, the methods for measuring the physical properties of the polyester resin, toner particles, and toner are as follows. In the examples described later, the physical properties are also measured based on these methods.
[0092] <Method of measuring toner softening point> The toner softening point was measured using a constant load extrusion type capillary rheometer, "Flow characteristic evaluation device The test is performed using a "Shimadzu Flow Tester CFT-500D" (Shimadzu Corporation) in accordance with the manual that comes with the device. With this device, a constant load is applied from above the measurement sample using a piston, while the measurement sample filled in a cylinder is heated and melted, and the molten measurement sample is extruded from a die at the bottom of the cylinder, and a flow curve showing the relationship between the piston descent amount and temperature can be obtained. In the present disclosure, the "melting temperature in the 1 / 2 method" described in the manual attached to the "Flow characteristic evaluation device Flow Tester CFT-500D" is defined as the softening point. The melting temperature in the 1 / 2 method is calculated as follows. First, 1 / 2 of the difference between the piston descent amount Ymax at the time when the outflow ends and the piston descent amount Ymin at the time when the outflow starts is calculated (this is defined as X; X=(Ymax-Ymin) / 2). Then, the temperature of the flow curve when the piston descent amount on the flow curve is the sum of X and Ymin is the melting temperature in the 1 / 2 method. The measurement sample is prepared by compressing approximately 1.6 g of toner at approximately 10 MPa for approximately 60 seconds using a tablet molding machine (e.g., NT-100H, manufactured by NPA Systems) in an environment of 25°C, and forming the toner into a cylindrical shape with a diameter of approximately 8 mm. The measurement conditions for the CFT-500D are as follows. Test mode: Temperature rise method Starting temperature: 50℃ Achieved temperature: 200℃ Measurement interval: 1.0℃ Heating rate: 4.0℃ / min Piston cross-sectional area: 1.000cm 2 Test load (piston load): 10.0kgf (0.9807MPa) Preheat time: 300 seconds Die hole diameter: 1.0mm Die length: 1.0mm
[0093] <Method of measuring ion amount (secondary ion mass / secondary ion charge number (m / z)) using time-of-flight secondary ion mass spectrometry (TOF-SIMS)> To measure the amount of ions (peak intensity) using TOF-SIMS, TRIFT-IV manufactured by ULVAC-PHI, Inc. is used. The analysis conditions are as follows. Sample preparation: Adhering toner to an indium sheet Sample preparation: None Primary ion: Au ion Acceleration voltage: 30 kV Charge neutralization mode: On Measurement mode: Positive Raster: 200μm Measurement time: 60s
[0094] Normally, TOF-SIMS is a surface analysis method, and the data in the depth direction is about 1 nm. Therefore, the intensity inside the toner particle is measured by argon gas cluster ions. -Measurements are performed by sputtering particles and scraping the surface. The sputtering conditions are as follows. Acceleration voltage: 10 kV Current: 3.4nA Raster: 600μm Irradiation time: 5s
[0095] The depth was measured in advance by sputtering a polymethyl methacrylate (PMMA) film under the same conditions to confirm the relationship with the irradiation time, and it was confirmed that an irradiation time of 300 s removes 100 nm of the surface. In the present disclosure, measurements are repeated once for each sputtering under the above conditions, and the intensity at a depth of 100 nm from the surface of the toner particles is the amount of ions measured after sputtering 60 times under the above conditions. The strength of the outermost surface of the toner particles is the value of the amount of ions measured without sputtering the toner particles after removing external additives from the toner by the method described below to obtain toner particles.
[0096] Calculation and definition of standard values, A(0), A(100), and A(dmax): According to the standard software (Win Cadense) of ULVAC-PHI, the total count number of 43.5 to 44.5, which is the mass number of the structure represented by formula (A), is defined as the amount of ions (secondary ion mass / secondary ion charge number (m / z)) of the structure represented by formula (A), and the value obtained by dividing this value by the total amount of ions counted in the toner measurement is defined as the standard value. The operation of calculating the standard value is performed for all ion amounts measured 60 times under the above conditions, and the vertical axis is plotted as the standard value and the horizontal axis is plotted as the depth d (nm) from the surface of the toner particle, to obtain a graph as shown in Figure 1. As described above, the standard value at the surface of the toner particles (0 nm deep from the surface of the toner particles) after removing the external additives from the toner is defined as A(0). The standard value at a depth of 100 nm from the surface of the toner particles is defined as A(100). Furthermore, among the standard values obtained by measuring the amount of ions from the surface of the toner particles to a depth of 100 nm, a standard value that is 1.05 times or more the value of A(0) and 1.05 times or more the value of A(100) is defined as a peak, and the maximum peak among them is defined as A(dmax).
[0097] <Removal of external additives> (1) In the case of non-magnetic toner Add 160 g of sucrose (Kishida Chemical) to 100 mL of ion-exchanged water and dissolve in a hot water bath to prepare a concentrated sucrose solution. Place 31 g of the concentrated sucrose solution and 6 mL of Contaminon N (a 10% by weight aqueous solution of a neutral detergent for cleaning precision measuring instruments, pH 7, consisting of a nonionic surfactant, anionic surfactant, and organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) in a centrifuge tube to prepare a dispersion. Add 1 g of toner to this dispersion and break up the toner clumps with a spatula or the like. The centrifuge tube is shaken for 30 minutes at 350 reciprocations per minute in the shaker. After shaking, the solution is transferred to a glass tube (50 mL) for a swing rotor and centrifuged at 58.33 S in a centrifuge (H-9R; manufactured by Kokusan Co., Ltd.). -1 Centrifugation is performed under the conditions of 100°C, 30 minutes. After centrifugation, the toner particles are present in the top layer of the glass tube, and the external additives are present in the aqueous solution at the bottom. The toner particles in the top layer are collected and filtered, and washed with 2 L of ion-exchanged water heated to 40°C, and the washed toner particles are taken out.
[0098] (2) Magnetic toner Add 6 mL of Contaminon N (a 10% by weight aqueous solution of a neutral detergent for cleaning precision measuring instruments, consisting of a nonionic surfactant, an anionic surfactant, and an organic builder, pH 7, manufactured by Wako Pure Chemical Industries, Ltd.) to 100 mL of ion-exchanged water to prepare a dispersion medium. Add 5 g of toner to this dispersion medium and disperse it for 5 minutes using an ultrasonic disperser (As One Corporation VS-150). Then, disperse the toner using a 100 mL of Iwaki-produced toner. The mixture was then set in a KM Shaker (model: V.SX) manufactured by SANYO KABUSHIKI KAISHA and shaken for 20 minutes at 350 strokes per minute. The toner particles are then bound and collected using a neodymium magnet. The toner particles are washed with 2 L of ion-exchanged water heated to 40°C, and the washed toner particles are taken out.
[0099] Gradient Polymer Elution Chromatography (GPEC) The sample used for the measurement was prepared by adjusting the resin concentration to 0.1% by mass using chloroform, and filtering the solution through a 0.45 μm polytetrafluoroethylene (PTFE) filter. The measurement conditions for gradient polymer elution chromatography (GPEC) are shown below. Equipment: ULTIMATE3000 (Thermo Fisher Scientific) Mobile phase: A Chloroform (HPLC), B Acetonitrile (HPLC) Gradient: 2min (A / B=0 / 100) → 25min (A / B=100 / 0) (The gradient of the mobile phase change was made linear.) Flow rate: 1.0mL / min Injection: 0.1% by mass x 20μL Column: Tosoh TSKgel ODS (4.6mmφ×150mm×5μm) Column temperature: 40℃ Detector: Corona Charged Aerosol Detector (Corona-CAD) (Thermo Fisher Scientific) In order to eliminate the influence of variations in peak intensity due to differences in detection sensitivity caused by the chemical species of each peak and the composition of the mobile phase during elution, etc., and to make it easier to compare samples, the vertical axis is normalized to the top of the peak with the maximum intensity on each chromatogram and adjusted to have the same display scale. When the standard value of the peak top with the maximum intensity obtained in the measurement is S(1), the standard value of the peak top with the next highest intensity is S(2). A peak is considered to have a standard value of 0.10 times or more of S(1), which is the standard value of the peak top with the maximum intensity.
[0100] <Method for measuring molecular weight of polyester resin> The molecular weight of the crystalline polyester is measured by gel permeation chromatography (GPC) as follows. First, the crystalline polyester is dissolved in tetrahydrofuran (THF) at room temperature. The resulting solution is then filtered through a solvent-resistant membrane filter "Myshoridisc" (manufactured by Tosoh Corporation) with a pore size of 0.2 μm to obtain a sample solution. The sample solution is adjusted so that the concentration of components soluble in THF is 0.8 mass%. This sample solution is used to perform measurements under the following conditions. Equipment: High-speed GPC equipment "HLC-8220GPC" [Tosoh Corporation] Column: LF-604 in two columns Eluent:THF Flow rate: 0.6ml / min Oven temperature: 40℃ Sample injection volume: 0.020 ml In calculating the molecular weight of the sample, a molecular weight calibration curve prepared using standard polystyrene resins (e.g., trade names "TSK Standard Polystyrene F-850, F-450, F-288, F-128, F-80, F-40, F-20, F-10, F-4, F-2, F-1, A-5000, A-2500, A-1000, A-500" manufactured by Tosoh Corporation) is used.
[0101] <Acid value of polyester resin> The acid value is the number of milligrams of potassium hydroxide required to neutralize the acid contained in 1 g of a sample. The acid value in this disclosure is measured in accordance with JIS K 0070-1992, and specifically, is measured according to the following procedure. Titration is performed using a 0.1 mol / l potassium hydroxide ethyl alcohol solution (Kishida Chemical Co., Ltd.). The factor of the potassium hydroxide ethyl alcohol solution can be determined using a potentiometric titrator (Kyoto Electronics Manufacturing Co., Ltd. Potentiometric titration measuring device AT-510). 100 ml of 0.100 mol / l hydrochloric acid is placed in a 250 ml tall beaker and titrated with the potassium hydroxide ethyl alcohol solution, and the factor is determined from the amount of the potassium hydroxide ethyl alcohol solution required for neutralization. The 0.100 mol / l hydrochloric acid used is prepared in accordance with JIS K 8001-1998.
[0102] The conditions for measuring the acid value are shown below. Titrator: Potentiometric titrator AT-510 (Kyoto Electronics Manufacturing Co., Ltd.) Electrode: Composite glass electrode double junction type (Kyoto Electronics Manufacturing Co., Ltd.) Control software for titrator: AT-WIN Titration analysis software: Tview The titration parameters and control parameters during titration are as follows: Titration parameters Titration mode: Blank titration Titration method: Total volume titration Maximum titration volume: 20ml Waiting time before titration: 30 seconds Titration direction: automatic Control parameters End point potential: 30dE End point potential: 50 dE / dmL End point detection judgment: Not set Control speed mode: Standard Gain: 1 Data collection potential: 4mV Data collection titration amount: 0.1ml
[0103] Main test: 0.100 g of the measurement sample is accurately weighed into a 250 ml tall beaker, 150 ml of a mixed solution of toluene / ethanol (3:1) is added, and the mixture is dissolved over 1 hour. Using the above potentiometric titration apparatus, titrate with the above potassium hydroxide ethyl alcohol solution. Blank test: Perform titration in the same manner as above, except that no sample is used (i.e., only a mixed solution of toluene / ethanol (3:1) is used). Substitute the obtained results into the following formula to calculate the acid value. A = [(CB) × f × 5.611] / S In the formula, A: acid value (mgKOH / g), B: amount of potassium hydroxide ethyl alcohol solution added for the blank test (ml), C: amount of potassium hydroxide ethyl alcohol solution added for the main test (ml), f: factor of the potassium hydroxide solution, and S: sample (g).
[0104] <Method for identifying each unit of polyester resin in toner particles and quantifying the content> For the above analysis, a pyrolysis gas chromatography mass spectrometer (hereinafter also referred to as pyrolysis GC / MS) and NMR are used. In this disclosure, components with a molecular weight of 1500 or more are measured. This is because the region of molecular weight less than 1500 is considered to be a region in which the proportion of wax is high and almost no resin components are contained. Pyrolysis GC / MS was used to determine all the constituent units in the polyester resin and The content of each unit can be determined from the peak area, but quantification requires normalization of the peak intensity using a reference sample of known concentration. On the other hand, NMR makes it possible to determine and quantify all of the constituent units in a polyester resin without using a sample of known concentration. Therefore, to identify the constituent units, the NMR and pyrolysis GC / MS spectra are compared depending on the situation. Specifically, when the amount of resin components that are insoluble in deuterated chloroform, which is the extraction solvent used in NMR measurement, is less than 5.0% by mass, quantification is performed by NMR measurement. On the other hand, if 5.0% by mass or more of resin components are present that are insoluble in deuterated chloroform, which is the extraction solvent used in the NMR measurement, both NMR and pyrolysis GC / MS measurements are performed on the deuterated chloroform soluble portion, and pyrolysis GC / MS measurement is performed on the deuterated chloroform insoluble portion. In this case, first, NMR measurement is performed on the deuterated chloroform soluble portion to identify and quantify the constituent units (quantitative result 1). Next, pyrolysis GC / MS measurement is performed on the deuterated chloroform soluble portion to determine the peak area of the peak attributable to each constituent unit. Using the quantitative result 1 obtained by the NMR measurement, the relationship between the amount of each constituent unit and the peak area of the pyrolysis GC / MS is obtained. Next, pyrolysis GC / MS measurement is performed on the deuterated chloroform insoluble portion to determine the peak area of the peak attributable to each constituent unit. From the relationship between the amount of each constituent unit obtained by the measurement of the deuterated chloroform soluble portion and the peak area of the pyrolysis GC / MS, the constituent units in the deuterated chloroform insoluble portion are quantified (quantitative result 2). Then, the quantitative result 1 and the quantitative result 2 are combined to form the final quantitative result for each constituent unit.
[0105] Specifically, the following operations are performed. (1) 500 mg of toner is weighed out into a 30 mL glass sample bottle, 10 mL of deuterated chloroform is added, the bottle is capped, and the toner is dispersed and dissolved for 1 hour using an ultrasonic disperser. The toner is then filtered through a 0.4 μm membrane filter, and the filtrate is collected. At this time, the deuterated chloroform insoluble matter remains on the membrane filter. (2) From 3 mL of the filtrate, components with a molecular weight of less than 1500 are removed using a fraction collector by preparative high performance liquid chromatography (HPLC), and a resin solution from which components with a molecular weight of less than 1500 have been removed is recovered. Chloroform is removed from the recovered solution using a rotary evaporator to obtain a resin. Note that the molecular weight of components with a molecular weight of less than 1500 is determined in advance by measuring a polystyrene resin with a known molecular weight and calculating the elution time. (3) 20 mg of the obtained resin was dissolved in 1 mL of deuterated chloroform, 1Perform H-NMR measurement, assign the spectra for each constituent unit used in the polyester resin, and obtain the quantitative values. (4) If analysis of the deuterated chloroform-insoluble fraction is necessary, perform the analysis by pyrolysis GC / MS. If necessary, perform derivatization treatment such as methylation.
[0106] <NMR Measurement Conditions> Measuring device: Bruker AVANCE 500 manufactured by Bruker BioSpin Corporation Measuring nucleus: 1 H Measuring frequency: 500.1 MHz Number of integrations: 16 times Measuring temperature: room temperature
[0107] <Pyrolysis GC / MS Measurement Conditions> Pyrolysis device: TPS-700 manufactured by JEOL Ltd. Pyrolysis temperature: appropriate value at 400 °C to 600 °C, 590 °C in this case GC / MS device: ISQ manufactured by Thermo Fisher Scientific K.K. Column: "HP5-MS" (Agilent / 19091S-433), length 30 m, inner diameter 0 .25 mm, film thickness 0.25 μm (GC / MS Conditions) Inlet conditions: InletTemp: 250 °C, SplitFlow: 50 ml / min GC temperature rising conditions: 40 °C (5 min) → 10 °C / min (300 °C) → 300 °C (20 min) Mass range: m / z = 10 to 550
[0108] <Method for Measuring Dielectric Dissipation Factor of Polyester Resin> Using a 4284A Precision LCR Meter (manufactured by Hewlett Packard), calculate the dielectric dissipation factor (tanδ = ε” / ε’) from the measured value of the complex dielectric constant at a frequency of 10,000 Hz. Weigh 0.3 g to 0.7 g of the polyester resin coarsely pulverized in a mortar, and 350 Kgf / cm 2The specimen is molded under a load of 350g for 2 minutes into a disk-shaped measurement specimen with a diameter of 25mm and a thickness of 1mm or less. This measurement specimen is measured three times at 25℃ in the frequency range of 1000Hz to 100000Hz with a load of 350g applied, using an ARES (manufactured by Rheometric Scientific F.E.) equipped with a 25mm diameter dielectric constant measurement jig (electrode). The dielectric constant is then obtained by calculating the average value of the measurements at 10000Hz for each measurement. When the polyester resin can be obtained alone, the measurement can be performed using the polyester resin. When only the toner is available, the polyester resin is isolated from the toner by carrying out the same operations as those (1) to (2) described in the identification of each unit of the polyester resin and the quantification of the content, and then the dielectric loss tangent is measured.
[0109] <Calculation method for average number of domains, number-average diameter of major axis and percentage of domains in crystalline materials> The number average diameter of the major axis of the domains of the crystalline material means the number average diameter determined from the major axis of the domains of the crystalline material based on a cross-sectional image of the toner observed with a transmission electron microscope (TEM). A toner cross section to be observed with a transmission electron microscope (TEM) is prepared as follows. The cross section of a toner particle is observed by staining the cross section with ruthenium. Since crystalline materials are less susceptible to ruthenium staining than amorphous resins, the contrast becomes clear and observation becomes easier. First, the toner is spread on a cover glass (Matsunami Glass Co., Ltd., square cover glass No. 1) so that it becomes a single layer, and an Os film (5 nm) and a naphthalene film (20 nm) are applied to the toner as a protective film using an osmium plasma coater (filgen, OPC80T). Next, a PTFE tube (Φ1.5 mm x Φ3 mm x 3 mm) is filled with photocurable resin D800 (JEOL Ltd.), and the cover glass is gently placed on top of the tube so that the toner is in contact with the photocurable resin D800. In this state, the resin is hardened by irradiating light, and then the cover glass and the tube are removed to form a cylindrical resin with the toner embedded in the outermost surface. Using an ultrasonic ultramicrotome (Leica, UC7), a cutting speed of 0.6 mm / s is used to cut the length of the radius of the toner particles (4.0 μm when the weight average particle size (D4) is 8.0 μm) from the outermost surface of the cylindrical resin to expose the cross section of the toner particles. Next, the toner particles were cut to a thickness of 250 nm for magnetic toner and 70 nm for non-magnetic toner, to prepare thin slice samples of the toner particle cross section. By cutting in this way, the cross section of the center of the toner particle can be obtained. The obtained thin section sample is stained for 15 minutes in a RuO4 gas atmosphere of 500 Pa using a vacuum electron staining apparatus (filgen, VSC4R1H), and then observed using a TEM (JEOL, JEM2800). The TEM probe size was 1 nm, and the image size was 1024 x 1024 pixels. Adjust st to 1425, Brightness to 3750, and in the Image Control panel adjust Contrast to 0.0, Brightness to 0.5, and Gamma to 1.00, and capture the image.
[0110] As described above, when the toner is stained with ruthenium, the crystalline material is not easily stained, so that the domains of the crystalline material appear black when observed by TEM. In this way, the domains of the crystalline material are identified. In calculating the number of domains of the crystalline material and the number-average diameter of the major axis, the cross sections of 100 or more toner particles are observed by the above method. The number and major axis of all crystalline material domains of the observed toner are measured, and the average number and number-average diameter of the major axis are calculated. The obtained number and number-average diameter are regarded as the number and number-average diameter of the domains of the crystalline material.
[0111] From the contour of a toner cross section, the ratio of crystalline domains present in an area that is 25% or less of the distance between the contour and the center of the cross section (25% ratio) is calculated as follows. The 25% ratio is the proportion (number %) of crystalline material present in a region within 25% of the distance from the contour of the cross section of a toner particle to the center point of the cross section. The calculation method for the 25% ratio is as follows: In the above TEM image, the outline and center point of the cross section of the toner particle are obtained by the method described later. The cross section of the toner particle to be observed is in the range of 0.9≦R The toner particle has a major axis R (μm) that satisfies the relationship of / D4≦1.1. The outline of the cross section of the toner particle is along the surface of the toner particle observed in the TEM image. The center point of the cross section of the toner particle is the center of gravity of the cross section of the toner particle. A line is drawn from the obtained center point to a point on the contour of the cross-section of the toner particle, and a position on the line that is 25% of the distance from the contour between the center point of the contour and the cross-section is identified. This operation is then performed around the contour of the toner particle cross section, and a boundary line that is 25% of the distance between the contour and the center point of the cross section is clearly indicated from the contour of the toner particle cross section (FIG. 4). Based on the TEM image in which the 25% boundary line is clearly indicated, the number of domains of the crystalline material in the cross section of one toner particle (hereinafter referred to as A) is counted. Also, the number of domains of the crystalline material present in a region within 25% of the distance between the contour of the toner particle cross section and the center point of the cross section (hereinafter referred to as B) is counted in the cross section of one toner particle. The domain of crystalline material existing on the above 25% boundary line is measured as "B" above. Next, the 25% ratio in the cross section of one toner particle is calculated by the following formula. 25% ratio in the cross section of one toner particle = {"B" / "A"} x 100 (%) This is carried out for the cross sections of 100 toner particles, and the arithmetic mean value is set to a 25% ratio.
[0112] <Calculation method for shell thickness in core-shell structure> In the TEM image of the ruthenium-stained toner cross section obtained by the above method, the part where no domain of crystalline material was observed near the toner surface (part not containing crystalline material) was defined as the shell. The cross sections of 100 or more toner particles were observed, and the average distance from the outline to the area not containing crystalline material was calculated, and this value was defined as the shell thickness.
[0113] <Method of measuring weight average particle diameter (D4) and number average particle diameter (D1) of toner> The weight-average particle size (D4) and number-average particle size (D1) of the toner were measured using a precision particle size distribution measuring device equipped with a 100 μm aperture tube, the "Coulter Counter Multisizer 3" (registered trademark, manufactured by Beckman Coulter, Inc.), which uses the narrow hole electrical resistance method, and the accompanying dedicated software "Beckman Coulter Multisizer 3 Version 3.51" (manufactured by Beckman Coulter, Inc.), for setting measurement conditions and analyzing measurement data, with an effective measurement channel count of 25,000. The measurement data was then analyzed. Calculate. The electrolyte solution used for the measurements is made by dissolving special grade sodium chloride in ion-exchanged water to a concentration of approximately 1% by mass; specifically, "ISOTON II" (manufactured by Beckman Coulter) is used. Before performing measurements and analysis, the dedicated software is set up as follows. In the "Change Standard Measurement Method (SOM) screen" of the dedicated software, set the total count number in the control mode to 50,000 particles, the number of measurements to 1, and the Kd value to the value obtained using "Standard Particle 10.0 μm" (Beckman Coulter). Press the threshold / noise level measurement button to automatically set the threshold and noise level. In addition, set the current to 1600 μA, the gain to 2, the electrolyte to ISOTON II, and check the aperture tube flush after measurement. In the "Pulse to particle size conversion setting screen" of the dedicated software, set the bin interval to logarithmic particle size, the particle size bin to 256 particle size bins, and the particle size range from 2 μm to 60 μm.
[0114] The specific measurement method is as follows. 1. Pour about 200 ml of the electrolyte solution into a 250 ml round-bottom glass beaker made exclusively for the Multisizer 3, set it on the sample stand, and stir the stirrer rod counterclockwise at 24 revolutions per second. Then, use the "aperture tube flush" function of the analysis software to remove dirt and air bubbles from inside the aperture tube. 2. Place approximately 30 ml of the above electrolyte solution in a 100 ml flat-bottom glass beaker, and add approximately 0.3 ml of a solution prepared by diluting "Contaminon N" (a 10% by weight aqueous solution of a neutral detergent for cleaning precision measuring instruments, consisting of a nonionic surfactant, an anionic surfactant, and an organic builder, with a pH of 7, manufactured by Wako Pure Chemical Industries, Ltd.) three times by weight with ion-exchanged water as a dispersant. 3. A specified amount of ion-exchanged water is placed in the water tank of an ultrasonic disperser "Ultrasonic Dispersion System Tetora150" (manufactured by Nikkaki Bios Co., Ltd.) that has two oscillators with an oscillation frequency of 50 kHz built in with a phase shift of 180 degrees and an electrical output of 120 W, and approximately 2 ml of the above-mentioned Contaminon N is added to this water tank. 4. Set the beaker from step 2 in the beaker fixing hole of the ultrasonic disperser and operate the ultrasonic disperser. Then, adjust the height of the beaker so that the resonance state of the electrolyte solution level in the beaker is maximized. 5. While the electrolyte solution in the beaker in step 4 is being irradiated with ultrasonic waves, about 10 mg of toner is added little by little to the electrolyte solution and dispersed. Then, ultrasonic dispersion treatment is continued for another 60 seconds. During ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted to be between 10°C and 40°C. 6. Using a pipette, add the electrolyte solution (5) in which the toner has been dispersed, to the round-bottom beaker (1) placed in the sample stand, and adjust the measurement concentration to about 5%. Then, measurements are continued until the number of particles measured reaches 50,000. 7. Analyze the measurement data using the dedicated software that comes with the device to calculate the weight average particle size (D4) and number average particle size (D1). Note that when the dedicated software is set to Graph / Number%, or Graph / Volume%, the "Arithmetic diameter" on the Analysis / Number Statistics (Arithmetic Mean) and Analysis / Volume Statistics (Arithmetic Mean) screens is the number average particle size (D1) and weight average particle size (D4), respectively. EXAMPLES
[0115] The present disclosure will be specifically described below with reference to examples, but the present disclosure is not limited thereto. In the following formulations, parts are by weight unless otherwise specified.
[0116] <Production Example of Polyester Resin 1> 100 parts of a mixture of raw material monomers other than trimellitic anhydride in the ratio shown in Table 1 below and 0.52 parts of tin di(2-ethylhexanoate) catalyst were placed in a polymerization tank equipped with a nitrogen introduction line, a dehydration line, and a stirrer. After the tank was conditioned in a nitrogen atmosphere, a polycondensation reaction was carried out over 6 hours while heating at 200°C. After the temperature was further increased to 210°C, trimellitic anhydride was added, and the pressure inside the polymerization tank was reduced to 40 kPa, after which a further condensation reaction was carried out to obtain a polyester resin. The acid value and weight average molecular weight (Mw) of the obtained polyester resin are shown in Table 1. Furthermore, when the obtained polyester resin was subjected to GPEC measurement, S(1) and S(2) were obtained as independent peaks. This resin was designated polyester resin 1.
[0117] <Production Examples of Polyester Resins 2 to 12> Polyester resins 2 to 12 were produced in the same manner as polyester resin 1, using the raw material monomer charging ratios shown in Table 1 below. Sampling and measurement were carried out successively, and when the desired molecular weight was reached, the polymerization reaction was stopped and the resin was taken out of the polymerization tank. The physical properties of the obtained resins are shown in Table 1 below. In addition, BPA used in polyester resin 9 was a mixture of bisphenol A propylene oxide 2 mole adduct and bisphenol A ethylene oxide 3 mole adduct in a molar ratio of 80.0:20.0 (bisphenol A propylene oxide 2 mole adduct: bisphenol A ethylene oxide 3 mole adduct = 80.0:20.0). When BPA was not specified, bisphenol A propylene oxide 2 mole adduct was used. By GPEC measurement, S(1) and S(2) were obtained as two independent peaks for polyester resins 2, 3, 4, 6, and 8. S(1) and S(2) were obtained as two overlapping peaks for polyester resins 5, 7, and 11. For polyester resins 9, 10, and 12, no peak that could define S(2) was obtained, so the S(2) / S(1) portion is not shown.
[0118] [Table 1]
[0119] *The monomer composition is indicated as a mass % ratio when the mass of the polyester composition is taken as 100. The abbreviations in the above table are: TPA: Terephthalic acid IPA: Isophthalic acid TMA: Trimellitic anhydride BPA: Bisphenol A EG: Ethylene glycol IS: Isosorbide
[0120] <Production Example of Polyester Resin 13> Bisphenol A propylene oxide 2 mole adduct: 469 parts Bisphenol A ethylene oxide 2 mole adduct: 137 parts Terephthalic acid: 152 parts Fumaric acid: 75 parts Dodecyl succinic acid: 114 parts
[0121] The above monomer components were placed in a reaction vessel equipped with a stirrer, thermometer, condenser and nitrogen gas inlet tube, 4 parts of dibutyltin oxide were added as a catalyst, nitrogen gas was introduced into the vessel to maintain an inert atmosphere and raise the temperature, after which a co-condensation reaction was carried out at 150°C to 230°C for 12 hours, and then the pressure was gradually reduced at 210°C to 250°C to synthesize polyester resin 13. The weight average molecular weight of the obtained polyester resin 13 was 10,500, the acid value was 12.4 mgKOH / g and the dielectric tangent was 0.0063. The obtained peak was 0.0066 m / s. by GPEC measurement. The peak consisted of two overlapping peaks, with an S(2) / S(1) ratio of 0.27.
[0122] <Preparation Example of Aqueous Dispersion 13 of Amorphous Polyester Resin Particles in the Absence of Organic Solvent> 200 parts of polyester resin 13 and 0.2 part of a 50% by mass aqueous solution of sodium hydroxide were charged into the raw material inlet of a twin-screw extruder (TEM-26SS, manufactured by Toshiba Machine Co., Ltd.). Further, from the fourth barrel of the twin-screw extruder, 4.1 parts of a 48.5% by mass aqueous solution of sodium dodecyl diphenyl ether disulfonic acid (ELEMINOL MON-7, manufactured by Sanyo Chemical Industries, Ltd.), which is a surfactant, was charged. Kneading was performed at a barrel temperature of 90°C and a screw rotation speed of 400 rpm to mix the polyester resin, sodium hydroxide, and surfactant. From the fifth barrel of the twin-screw extruder, 150 parts of ion-exchanged water adjusted to 90°C (ion-exchanged water 1), from the seventh barrel, 150 parts of ion-exchanged water adjusted to 90°C (ion-exchanged water 2), and from the ninth barrel, 150 parts of ion-exchanged water adjusted to 90°C (ion-exchanged water 3) were added and kneaded to obtain an aqueous dispersion 13 of amorphous polyester resin particles. The volume average particle diameter D50v of the resin particles was 179 nm. Also, the solid content concentration was adjusted to 25.0% by mass with ion-exchanged water.
[0123] <Production of WAX1> Into a reaction vessel equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, 100 parts of stearic acid and 10 parts of stearyl alcohol were added, and under a nitrogen stream, the reaction water was distilled off at 180°C while reacting at normal pressure for 15 hours. To 100 parts of the crude esterification product obtained by this reaction, 20 parts of toluene and 4 parts of ethanol were added. After stirring and allowing to stand for 30 minutes, the aqueous phase (lower layer) separated from the ester phase was removed to wash the crude esterification product with water. The above water washing was repeated 4 times until the pH of the aqueous phase reached 7. Then, under reduced pressure conditions of 170°C and 5 kPa, the solvent was distilled off from the water-washed ester phase to obtain WAX1.
[0124] <Production of WAX2> The same operations as in the production of WAX1 were performed except that the acid monomer was changed from stearic acid to behenic acid and the alcohol monomer was changed from stearyl alcohol to behenyl alcohol to obtain WAX2.
[0125] <Production of Crystalline Polyester Resin 1> Into a reaction vessel equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, 100.0 parts of sebacic acid as acid monomer 1, 1.6 parts of stearic acid as acid monomer 2, and 89.3 parts of 1,9-nonanediol as an alcohol monomer were charged. The temperature was raised to 140°C with stirring, and the mixture was heated to 140°C under a nitrogen atmosphere and reacted for 8 hours while distilling off water under normal pressure. After adding 0.57 parts of tin dioctylate, the mixture was reacted while heating to 200°C at a rate of 10°C / hour. After the reaction was continued for 2 hours after reaching 200°C, the pressure in the reaction vessel was reduced to 5 kPa or less, and the reaction was continued at 200°C while monitoring the molecular weight, to obtain crystalline polyester resin 1. When the obtained crystalline polyester resin 1 was analyzed, it was found to have a weight average molecular weight of 38,000.
[0126] <Production of Crystalline Polyester Resin 2> 1,10-Decanedioic acid (dodecanedioic acid): 241 parts 1,9-nonanediol: 174 parts The monomer components were placed in a reaction vessel equipped with a stirrer, a thermometer, a condenser and a nitrogen gas inlet tube, and the inside of the reaction vessel was replaced with dry nitrogen gas. Then, 0.25 parts of titanium tetrabutoxide (reagent) was added per 100 parts of the monomer components, and the mixture was stirred and reacted at 170°C for 3 hours under a nitrogen gas stream. The temperature was then raised to 210°C, the pressure in the reaction vessel was reduced to 3 kPa, and the mixture was stirred and reacted under reduced pressure for 13 hours to obtain crystalline polyester resin 2. The weight average molecular weight (Mw) of the obtained crystalline polyester resin 2 was 17,200. The acid value of the crystalline polyester resin 2 was 11.4 mgKOH / g. The crystalline melting point of the crystalline polyester resin 2 was 75°C.
[0127] <Preparation of Aqueous Dispersion 2 of Crystalline Polyester Resin Particles in the Presence of Organic Solvent> Crystalline polyester resin 2: 100 parts Ethyl acetate: 70 parts Isopropyl alcohol: 15 parts The ethyl acetate and isopropyl alcohol were added to a separable flask, and the crystalline polyester resin 2 was gradually added to this mixed medium and stirred with a three-one motor to completely dissolve the mixture, obtaining an oil phase. A 10% by mass aqueous ammonia solution was gradually added to the oil phase with a dropper so that the total amount was 3 parts, and 230 parts of ion-exchanged water was gradually added dropwise at a rate of 10 ml / min to cause phase inversion emulsification, and the solvent was removed while reducing the pressure with an evaporator, obtaining an aqueous dispersion 2 of crystalline polyester resin particles. The volume average particle diameter D50v of the resin particles was 165 nm, and the solid content was adjusted to 25.0% by mass with ion-exchanged water.
[0128] <Preparation of release agent dispersion> Release agent (manufactured by Nippon Seiro Co., Ltd., product name: FNP0090, melting point 89.7°C): 270 parts Anionic surfactant (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., Neogen RK, active ingredient amount: 60% by mass): 13.5 parts (as an active ingredient, 3.0% by mass relative to the release agent) Ion-exchanged water: 721.6 parts The above components were mixed, and the release agent was dissolved in a pressure discharge homogenizer (Gaulin homogenizer, manufactured by Gaulin Co., Ltd.) at an internal liquid temperature of 120°C. The mixture was then dispersed at a dispersion pressure of 5 MPa for 120 minutes, then at 40 MPa for 360 minutes, and cooled to obtain a release agent dispersion. The volume average particle size D50v of the particles in this dispersion was 230 nm. Then, ion-exchanged water was added to adjust the solid content concentration to 20.0 mass%, and a release agent dispersion was obtained.
[0129] (Preparation of Colorant Dispersion) Cyan pigment (Dainichi Seika Chemicals Co., Ltd.: ECB301): 200 parts Anionic surfactant (Neogen SC, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.): 33 parts (60% by weight of active ingredient, 10% by weight based on cyan pigment) -Ion-exchanged water: 750 parts 280 parts of ion-exchanged water and 33 parts of anionic surfactant are placed in a stainless steel container so that the liquid level is about 1 / 3 of the height of the container when all of the above ingredients are added. After the surfactant is sufficiently dissolved, 200 parts of the cyan pigment are added and mixed with a stirrer until it is wet. The mixture was stirred until no undissolved pigment remained, and was thoroughly defoamed. After defoaming, the remaining ion-exchanged water was added, and the mixture was dispersed for 10 minutes at 5,000 rpm using a homogenizer (Ultra Turrax T50, manufactured by IKA Co., Ltd.), and then stirred overnight with a stirrer for defoaming. After defoaming, the mixture was dispersed again for 10 minutes at 6,000 rpm using a homogenizer, and then stirred overnight with a stirrer for defoaming. The dispersion was then dispersed at a pressure of 240 MPa using a high-pressure impact disperser Ultimizer (HJP30006, manufactured by Sugino Machine Co., Ltd.). The dispersion was carried out for 10 passes, calculated from the total amount charged and the processing capacity of the device. The obtained dispersion was left for 72 hours to remove precipitates, and ion-exchanged water was added to adjust the solid content concentration to 15% by mass. The volume average particle size D50v of the particles in this colorant dispersion was 115 nm. The volume average particle diameter D50v was determined by averaging three measured values excluding the maximum and minimum values out of five measured values by a Microtrac.
[0130] (Preparation of Aluminum Sulfate Aqueous Solution) Aluminum sulfate powder (Asada Chemical Industry Co., Ltd.: 17% by weight aluminum sulfate): 35 parts Ion-exchanged water: 1,965 parts The aluminum sulfate powder and ion-exchanged water were placed in a container and stirred at 30° C. until the precipitate disappeared, to prepare an aqueous aluminum sulfate solution as a flocculant.
[0131] <Magnetic material 1: Example of manufacturing magnetic iron oxide> Fe 2+ 50 L of an aqueous solution of ferrous sulfate containing 2.0 mol / L was mixed with 55 L of an aqueous solution of sodium hydroxide containing 4.0 mol / L, and stirred to obtain an aqueous solution of ferrous salt containing ferrous hydroxide colloid. This aqueous solution was kept at 85°C and an oxidation reaction was carried out while blowing in air at 20 L / min, to obtain a slurry containing core particles. The obtained slurry was filtered and washed with a filter press, and the core particles were dispersed again in water to reslurry. Sodium silicate equivalent to 0.20 mass% of silicon per 100 parts of core particles was added to this reslurry liquid, the pH of the slurry liquid was adjusted to 6.0, and the mixture was stirred to obtain magnetic iron oxide particles with a silicon-rich surface. The obtained slurry was filtered and washed with a filter press, and further reslurried with ion-exchanged water. 500g (10 mass% relative to magnetic iron oxide) of ion-exchange resin SK110 (manufactured by Mitsubishi Chemical) was added to this reslurry liquid (solid content 50g / L) and stirred for 2 hours to perform ion exchange. Thereafter, the ion-exchange resin was removed by filtration with a mesh, filtered and washed with a filter press, dried and crushed to obtain magnetic material 1 (magnetic iron oxide) with a number average diameter of 0.23 μm.
[0132] <Toner 1 Manufacturing Example> The toner particles and toner were prepared according to the following procedure. 450 parts of 0.1 mol / L-Na3PO4 aqueous solution was added to 720 parts of ion-exchanged water and heated to 60°C, after which 67.7 parts of 1.0 mol / L-CaCl2 aqueous solution was added to obtain an aqueous medium containing a dispersion stabilizer. (Preparation of Polymerizable Monomer Composition) Styrene 74.0 parts n-Butyl acrylate 26.0 parts 1,6-Hexanediol diacrylate 0.6 parts ·Magnetic material 1 90 parts Polyester resin 1 4.0 parts The above materials were uniformly dispersed and mixed using an attritor (manufactured by Mitsui Miike Chemical Engineering Co., Ltd.), then heated to 60°C, and 20.0 parts of WAX1 as an ester wax and 10.0 parts of paraffin wax (manufactured by Nippon Seiro Co., Ltd., HNP-51) as a hydrocarbon wax were added, mixed, and dissolved to obtain a polymerizable monomer composition. The monomer composition was added to the aqueous medium, and the mixture was heated at 60° C. under a N2 atmosphere. The mixture was stirred at 12,000 rpm for 10 minutes in a homogenizer (manufactured by Tokushu Kika Kogyo Co., Ltd.) to form granules. Then, 8.0 parts of a polymerization initiator, t-butyl peroxypivalate, was added while stirring with a paddle impeller, and the mixture was heated to 74° C. and reacted for 3 hours. After the reaction was completed, the suspension was heated to 100°C as the high-temperature high-pH treatment step described above, and the suspension was kept at pH (1) of 5.0 for 2 hours. Then, while the suspension was still at 100°C, 0.9 mol / L-Na2CO3 aqueous solution was added to adjust the suspension's pH (2) to 8.0 and kept at that temperature for 30 minutes. Then, as a cooling step, 7°C water was added to the suspension, and the suspension was cooled from 100°C to 45°C at a rate of 200°C / min, and then kept at 48°C for 3 hours. Then, the suspension was naturally cooled to 25°C at room temperature. The cooling rate at that time was 2°C / min. Then, hydrochloric acid was added to the suspension and the suspension was thoroughly washed to dissolve the dispersion stabilizer, and the suspension was filtered and dried to obtain toner particles 1 having a weight average particle size (D4) of 7.2 μm. The following materials were mixed with 100 parts of toner particles 1 in a Henschel mixer (FM-10 type, manufactured by Mitsui Miike Chemical Engineering Co., Ltd.) to obtain toner 1. 0.5 parts by mass of hydrophobic silica particles with a number-average primary particle size of 20 nm that have been surface-treated with 25% by mass of hexamethyldisilazane 0.5 parts by mass of hydrophobic silica particles with a number-average primary particle size of 40 nm that have been surface-treated with 15% by mass of hexamethyldisilazane The physical properties of the obtained toner 1 are shown in Table 4.
[0133] <Toner 2 Manufacturing Example> The following materials were charged into an attritor (Mitsui Miike Chemical Engineering Co., Ltd.), and dispersed for 5 hours at 220 rpm using zirconia particles with a diameter of 1.7 mm to obtain a pigment master batch: 60.0 parts of styrene Carbon black (Orion Engineered Carbons, product name "Printex35") 7 parts Charge control agent (Orient Co., Ltd.: Bontron E-89) 0.10 parts
[0134] 450 parts of 0.1 mol / L-Na3PO4 aqueous solution was added to 720 parts of ion-exchanged water and heated to 60°C, after which 67.7 parts of 1.0 mol / L-CaCl2 aqueous solution was added to obtain a dispersion stabilizer. An aqueous medium containing the polymerizable monomer composition was obtained. Styrene 14.0 parts n-Butyl acrylate 26.0 parts 1,6-Hexanediol diacrylate 0.6 parts Pigment masterbatch 67.1 parts Polyester resin 1 4.0 parts
[0135] The subsequent steps were the same as in the production example of toner 1, to obtain toner 2. The physical properties of the obtained toner are shown in Table 4.
[0136] <Toner 3 and 4 manufacturing example> Toners 3 and 4 were obtained by carrying out the same operations as in the production example of Toner 1, except that the material composition of Toner 1 was changed as shown in Table 2, and the temperature and pH of the suspension in the high-temperature, high-pH treatment step, the cooling start temperature, cooling rate and cooling end temperature of the suspension in the cooling step, and the annealing temperature were changed as shown in Table 3. The physical properties of the obtained toners are shown in Table 4.
[0137] <Production Examples of Toners 5 to 8> Toners 5 to 8 were obtained in the same manner as in the production example of Toner 1, except that the amount of polyester resin 1 in Toner 1 was changed as shown in Table 2. The physical properties of the obtained toners are shown in Table 4.
[0138] <Production Example of Toner 9> Polyester resin 1: 100.0 parts Colorant Magnetic material 1: 60.0 parts Crystalline polyester resin 1: 20.0 parts Release agent Release agent 1 (C105, manufactured by Sasol, melting point 105°C): 2.0 parts Charge control agent T-77 (manufactured by Hodogaya Chemical Co., Ltd.): 2.0 parts The above materials were premixed in an FM mixer (manufactured by Nippon Coke Industry Co., Ltd.), and then melt-kneaded using a twin-screw kneading extruder (manufactured by Toshiba Machine Co., Ltd., TEM-26SS, φ26 mm, L / D=48). The kneading feed was set to 20 kg / h, the rotation speed was set to 200 rpm, and the die temperature and the kneader heater temperature were adjusted so that the temperature of the resin discharged from the die was 150°C. The resulting kneaded material was cooled, coarsely pulverized using a hammer mill, and then pulverized using a mechanical pulverizer (T-250 manufactured by Turbo Kogyo Co., Ltd.). The resulting finely pulverized powder was classified using a multi-division classifier utilizing the Coanda effect, and then surface-treated using a mechanical surface treatment device (Faculty F-400 manufactured by Hosokawa Micron Corporation). The surface treatment conditions were a dispersion rotation speed of 5500 rpm, a classifying rotation speed of 7000 rpm, the number of hammers was 8, the treatment weight per batch was 200 g, and the treatment time was 60 seconds. As a result, resin particles 9 having a weight average particle size (D4) of 6.8 μm were obtained. 450 parts of 0.1 mol / L-Na3PO4 aqueous solution was added to 720 parts of ion-exchanged water and heated to 60°C under a N2 atmosphere, and then 67.7 parts of 1.0 mol / L-CaCl2 aqueous solution was added to obtain an aqueous medium containing a dispersion stabilizer. Resin particles 9 were added to an aqueous medium and uniformly dispersed and mixed using an attritor (manufactured by Mitsui Miike Chemical Engineering Co., Ltd.) to obtain a suspension. While stirring the obtained suspension with a paddle stirring blade, the suspension was heated to 100°C as the above-mentioned high-temperature high-pH treatment step, and the suspension was kept at pH (1) of 5.0 for 2 hours. After that, while the suspension was still at 100°C, 0.9 mol / L-Na2CO3 aqueous solution was added to adjust the suspension's pH (2) to 8.0 and kept for 30 minutes. Then, as a cooling step, 7°C water was added to the dispersion liquid, and the suspension was cooled from 100°C to 45°C at a rate of 200°C / min, and then kept at 48°C for 3 hours. Then, the suspension was naturally cooled to 25°C at room temperature. The cooling rate at that time was 2°C / min. Then, hydrochloric acid was added to the suspension and thoroughly washed to dissolve the dispersion stabilizer, and the suspension was filtered and dried to obtain toner particles 9 with a weight average particle size (D4) of 6.9 μm. The following materials were mixed in a Henschel mixer (FM-10, manufactured by Mitsui Miike Chemical Engineering Co., Ltd.) for 100 parts of toner particles 9 while maintaining the temperature at 25° C. and humidifying to 70% RH, to obtain toner 9. 0.5 parts of hydrophobic silica particles with a number-average primary particle size of 20 nm that have been surface-treated with 25% by mass of hexamethyldisilazane 0.5 parts of hydrophobic silica particles with a number-average primary particle size of 40 nm that have been surface-treated with 15% by mass of hexamethyldisilazane The physical properties of the obtained toner 9 are shown in Table 4.
[0139] <Production Example of Toner 10> (Preparation of polymer dispersion) Toluene 300.0 parts Polyester resin 1 100.0 parts The above materials were weighed, mixed, and dissolved at 90°C. Separately, 5.0 parts of sodium dodecylbenzenesulfonate and 10.0 parts of sodium laurate were added to 700.0 parts of ion-exchanged water and dissolved by heating at 90°C. Next, the toluene solution and the aqueous solution were mixed together and stirred at 7000 rpm using an ultra-high speed stirrer TK Robomix (manufactured by Primix). In addition, a high-pressure impact dispersing machine Nanomizer (manufactured by Yoshida Kikai Kogyo) was used to disperse the mixture at a pressure of 200 MPa. Thereafter, the toluene was removed using an evaporator, and the concentration was adjusted with ion-exchanged water to obtain a polymer dispersion having a polymer particle concentration of 20 mass %. (Preparation of Crystalline Material Dispersion) Crystalline polyester resin 1 100.0 parts Anionic surfactant Neogen RK (manufactured by Daiichi Kogyo Seiyaku) 5.0 parts Ion-exchanged water 395.0 parts The above materials were weighed and placed in a mixing vessel equipped with an agitator, then heated to 90°C and circulated through a Clearmix W Motion (manufactured by M Technique) for 60 minutes to perform dispersion processing. The dispersion processing conditions were as follows: Rotor outer diameter: 3cm Clearance: 0.3mm Rotor speed: 19000 r / min Screen rotation speed: 19000 r / min After the dispersion process, the mixture was cooled to 40°C under cooling conditions of a rotor rotation speed of 1000 r / min, a screen rotation speed of 0 r / min, and a cooling rate of 10°C / min to obtain a crystalline material dispersion with a crystalline material concentration of 20% by mass. (Preparation of magnetic material dispersion) ·Magnetic material 1 50.0 parts -Ion-exchanged water 450.0 parts The above materials were weighed, mixed, and dispersed for about 1 hour using a high-pressure impact disperser Nanomizer (manufactured by Yoshida Kikai Kogyo Co., Ltd.) to obtain a magnetic material dispersion with a magnetic particle concentration of 10 mass %. (Toner manufacturing) ·Polymer dispersion liquid 400.0 parts ·Crystalline material dispersion liquid 16.0 parts ·Magnetic dispersion liquid 480.0 parts Ion-exchanged water 100.0 parts The above materials were placed in a round stainless steel flask and mixed. Next, the mixture was dispersed at 5000 rpm for 10 minutes using a homogenizer Ultra Turrax T50 (manufactured by IKA). After adding a 1.0% aqueous nitric acid solution to adjust the pH to 3.0, the mixture was heated to 58°C in a heating water bath using a stirring blade while appropriately adjusting the rotation speed so that the mixture was stirred. The volume average particle size of the formed aggregated particles was appropriately confirmed using a Coulter Multisizer III, and when aggregated particles with a volume average particle size of about 6.0 μm were formed, the mixture was stirred for 2 hours at 58° C. with a 5% aqueous sodium hydroxide solution at a pH of 6.0. The mixture was then heated to 100° C. and stirred for an additional 2 hours at a pH (1) of 5.0 at 100° C., and a 5% aqueous sodium hydroxide solution was added to adjust the pH (2) to 8.0 and maintained for 30 minutes. Thereafter, the mixture was cooled to 50° C. and held at that temperature for 3 hours to promote crystallization of the polymer. Thereafter, the mixture was cooled to 25° C., filtered and separated into solid and liquid, and then washed with ion-exchanged water. After washing, the particles were dried using a vacuum dryer to obtain toner particles 10 having a weight average particle size of 6.8 μm. The following materials were mixed with respect to 100 parts of toner particles 10 in a Henschel mixer (FM-10 type, manufactured by Mitsui Miike Kakoki Co., Ltd.) to obtain toner 10. 0.5 parts of hydrophobic silica particles with a number-average primary particle size of 20 nm that have been surface-treated with 25% by mass of hexamethyldisilazane 0.5 parts of hydrophobic silica particles with a number-average primary particle size of 40 nm that have been surface-treated with 15% by mass of hexamethyldisilazane The physical properties of the obtained toner 10 are shown in Table 4.
[0140] <Production Example of Toner 11 to 15> Toners 11 to 15 were obtained by the same operations as in the production example of Toner 1, except that the material composition of Toner 1 was changed as shown in Table 2, and the temperature and pH of the suspension in the high-temperature high-pH treatment step, the cooling start temperature, cooling rate and cooling end temperature of the suspension in the cooling step, and the annealing temperature were changed as shown in Table 3. The physical properties of the obtained toners are shown in Table 4.
[0141] <Production Example of Toner 16> Toner 16 was obtained by the same procedure as in Production Example of Toner 1, except that in Production Example of Toner 1, the 0.9 mol / L-Na2CO3 aqueous solution was not added to the suspension, the material composition was changed as shown in Table 2, and the pH of the suspension when heated to 100°C was changed as shown in Table 3. The physical properties of the obtained toner are shown in Table 4.
[0142] <Toner 17 Manufacturing Example> In the manufacturing example of toner 9, the material composition was changed as shown in Table 2, the obtained finely pulverized powder was classified using a multi-division classifier utilizing the Coanda effect, and then surface-modified using the surface-modifying device shown in FIG. 5 to obtain resin particles, and the obtained resin particles were directly used as toner particles without any operation in an aqueous medium, but otherwise the same operation as for toner 9 was carried out to obtain toner 17. The physical properties of the obtained toner are shown in Table 4. The conditions for surface modification using the surface-modifying device shown in FIG. 5 are as follows. (Conditions for surface modification) Raw material supply rate 2.0kg / hr Hot air flow rate 4.5m 3 / min Hot air discharge temperature 220℃ Cold air temperature 3℃ Cold air flow rate 3.0m 3 / min
[0143] <Toner 18 Manufacturing Example> In the production example of Toner 9, the material composition was changed as shown in Table 2, and the obtained resin particles were not subjected to any operation in an aqueous medium, but were used as they were as toner particles. The same operation as for Toner 9 was performed to obtain Toner 18. The physical properties of the obtained toner are shown in Table 4.
[0144] <Production Example of Toner 19-21> Toners 19 to 21 were obtained by carrying out the same operations as in the production example of Toner 1, except that the material composition of Toner 1 was changed as shown in Table 2, and the temperature and pH of the suspension in the high-temperature high-pH treatment step, the cooling start temperature, cooling rate and cooling end temperature of the suspension in the cooling step, and the annealing temperature were changed as shown in Table 3. The physical properties of the obtained toners are shown in Table 4.
[0145] <Production Example of Toner 22 and 23> Toners 22 and 23 were obtained by the same operations as in the production example of Toner 2, except that the material composition of Toner 2 was changed as shown in Table 2, and the temperature and pH of the suspension in the high-temperature high-pH treatment step, the cooling start temperature, cooling rate and cooling end temperature of the suspension in the cooling step, and the annealing temperature were changed as shown in Table 3. The physical properties of the obtained toners are shown in Table 4.
[0146] <Toner 24 Manufacturing Example> Toner 24 was obtained by the same procedure as in the production example of Toner 1, except that the material composition of Toner 1 was changed as shown in Table 2, and the temperature and pH of the suspension in the high-temperature, high-pH treatment step, the cooling start temperature, cooling rate and cooling end temperature of the suspension in the cooling step, and the annealing temperature were changed as shown in Table 3. The physical properties of the obtained toner are shown in Table 4.
[0147] <Toner 25 Manufacturing Example> In the production example of Toner 9, Polyester Resin 1 was changed to Polyester Resin 9, and the obtained resin particles were not subjected to any operation in an aqueous medium, but were used as they were as toner particles, and the same operation as for Toner 9 was carried out to obtain Toner 25. The physical properties of the obtained toner are shown in Table 4.
[0148] <Toner 26 Manufacturing Example> (Addition of ammonium compounds) As the ammonium compound, a 10% by mass aqueous ammonia solution was used. After preparing the aqueous dispersion 2 of the crystalline polyester resin particles, a 10% by mass aqueous ammonia solution was added to the aqueous dispersion 2 of the crystalline polyester resin so that the amount of the ammonium compound was 2.5 parts per 1,000 parts of the crystalline polyester resin 2, and the mixture was stirred for 3 minutes. Furthermore, after preparing an aqueous dispersion 13 of amorphous polyester resin particles, a 10% by mass aqueous ammonia solution was also added to this aqueous dispersion 13 of amorphous polyester resin particles so that the ammonium compound was 2.5 parts per 1,000 parts of polyester resin 13, and the mixture was stirred for 3 minutes.
[0149] (Adjustment of dispersion liquid of toner components) After the ammonium compound was added, the following components were placed in a stirring vessel equipped with a thermometer, pH meter, stirrer, and jacket, and stirred for 10 minutes. Aqueous dispersion of crystalline polyester resin particles with added ammonium compound 2:57 parts Aqueous dispersion of amorphous polyester resin particles with added ammonium compound 13: 635 parts Colorant dispersion: 100 parts Release agent dispersion: 115 parts -Ion-exchanged water: 200 parts Anionic surfactant (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., Neogen RK): 7.0 parts While gradually adding 125 parts of an aqueous aluminum sulfate solution to the above dispersion mixture placed in a stirring tank, the mixture was introduced into a Cavitron CD1010 (made by Eurotech Co., Ltd.) through the bottom valve of the stirring tank and dispersed for 10 minutes. After the addition was completed, the jacket temperature was increased to 50°C and heating was started. After 120 minutes, the particle size was measured with a Multisizer II (aperture diameter: 50 μm, made by Beckman Coulter, Inc.) and found to be 5.0 μm in volume average particle size. Then, 312 parts of the aqueous dispersion 13 of amorphous polyester resin particles for addition was added and held for 30 minutes. Then, a 4% by mass aqueous sodium hydroxide solution was added to the stirring tank to adjust the pH to 9.0, and the jacket temperature was raised to 90°C and held at that temperature. The shape and surface properties of the aggregated particles were observed every 30 minutes using an optical microscope and a scanning electron microscope (FE SEM), and coalescence of the particles was confirmed after 4 hours, so the obtained slurry was cooled to 40°C. The cooled slurry was sieved using a vibrating sieve (KGC800: manufactured by Kowa Kogyo Co., Ltd.) with 15 μm mesh, and then filtered using a filter press (manufactured by Tokyo Engineering Kogyo Co., Ltd.). Then, ion-exchanged water in an amount 10 times the mass of the toner was passed through the toner in the filter press device to wash the toner. The washed toner was dried using a loop-type airflow dryer (manufactured by Seishin Enterprise Co., Ltd.). The mixture was dried using a flash jet dryer FJD-2 and cyclone collection to obtain toner particles. To 100 parts of the obtained toner particles, 1.0 part of hydrophobic silica (manufactured by Nippon Aerosil Co., Ltd., RY50) and 0.8 parts of hydrophobic titanium oxide (manufactured by Nippon Aerosil Co., Ltd., T805) were added and mixed for 30 seconds at 13,000 rpm using a sample mill. The mixture was then sieved using a vibrating sieve with 45 μm openings to obtain a toner.
[0150] <Preparation of carrier> Mn-Mg-Sr ferrite particles (average particle size 40 μm): 100 parts Toluene: 14 parts Cyclohexyl methacrylate / dimethylaminoethyl methacrylate copolymer (copolymer mass ratio 99:1, weight average molecular weight Mw 80,000): 2.0 parts Carbon black (VXC72: manufactured by Cabot Corporation): 0.12 parts The above components except for the ferrite particles and glass beads (φ1 mm, the same amount as toluene) were stirred at 1,200 ppm for 30 minutes using a sand mill manufactured by Kansai Paint Co., Ltd. to prepare a solution for forming a resin coating layer. Furthermore, this solution for forming a resin coating layer and the ferrite particles were placed in a vacuum degassing kneader, the pressure was reduced, and the toluene was distilled off / dried to form a resin-coated carrier.
[0151] (Preparation of Toner 26) 40 parts of the toner were added to 500 parts of the resin-coated carrier, and the mixture was blended in a V-type blender for 20 minutes. After that, aggregates were removed using a vibrating sieve with 212 μm openings, and toner 26 was obtained.
[0152] [Table 2]
[0153] St represents styrene, BA represents n-butyl acrylate, and St / BA represents the mass ratio of styrene to n-butyl acrylate in the core.
[0154] [Table 3]
[0155] [Table 4]
[0156] *1,2: If no value is stated, it means that no clear peak value was detected. *3: If there is no description, it means that there is no clear shell.
[0157] Next, examples and comparative examples will be described in detail. <Example 1> Toner 1 was used to carry out the following evaluations. (Evaluation 1) Fixability Evaluation 1 (Low Temperature Fixability) The evaluation was carried out in an environment of 23°C and 50% RH. The fixing media was FOX RIVER. BOND paper (110g / m 2 ) was used. By using a medium that has a relatively large surface irregularity and is thick paper, the white spots described below tend to occur easily, making it possible to strictly evaluate low-temperature fixing properties. The image forming device used was a commercially available LBP-3100 (Canon) that was modified to change the print speed from 16 sheets / minute to 40 sheets / minute and with the fixing unit removed. At room temperature (25°C), the toner load on the paper is 9 g / m 2 After adjusting the temperature to be 100 times or more, 100 sheets of solid black images were printed continuously in an unfixed state. After that, the 95th to 100th unfixed solid black images were fixed using a modified fixing device in which the fixing unit was modified so that the fixing temperature could be adjusted, and the average number of white spots was measured. By continuously printing solid black images, the heat of the fixing device is taken by the media, resulting in a state in which sufficient heat is not retained, and this results in a strict evaluation of the low-temperature fixing ability of the toner. If the low-temperature fixing ability of the toner is insufficient, a so-called white spot image in which the unfixed toner is white is output. Using a microscope or the like that can be magnified 10 times or more, a total of six fixed solid black images from the 95th to 100th sheets were visually observed, and the average number of white spots that occurred was measured. In this evaluation, the fixing performance was evaluated based on the temperature of the fixing device at which the average number of white spots was less than 10. The lower this temperature, the better the low-temperature fixing ability of the toner. The evaluation results are shown in Table 5. It was determined that the effects of the present disclosure were obtained if the temperature was 205° C. or lower.
[0158] (Evaluation 2) Fixation Evaluation 2 (Adhesion to paper) The fixing media is FOX RIVER BOND paper (110g / m 2) was used, and a commercially available LBP-3100 (Canon) was modified to change the print speed from 16 sheets / minute to 40 sheets / minute, remove the fixing unit, and make it possible to adjust the developing bias. The evaluation image was a line image. By increasing the reflection density of the image area by varying the development bias, the amount of toner on the image is increased, and by using thick paper with a relatively uneven surface, the toner in the recesses of the paper and the lower part of the toner layer is less likely to melt during the fixing process, allowing for a strict evaluation of peeling. As for the evaluation environment, a low temperature makes it difficult for the fixing unit to warm up, resulting in a strict evaluation. The evaluation procedure is as follows. First, the image forming apparatus and the modified fixing device, which had been modified so that the fixing temperature could be adjusted, were left overnight in a low-temperature, low-humidity environment (temperature 15°C, humidity 10%). After that, the image forming apparatus was used to measure the toner amount on the paper using FOX RIVER BOND paper at 9 g / m2. 2 Then, an unfixed horizontal line image was printed with the development bias adjusted so that the line width was 180 μm. Next, the fixing temperature of the modified fixing device was set to 205° C., and the unfixed horizontal line image was fixed. After leaving the fixed line image in a low temperature and low humidity environment for 1 hour, a polypropylene tape (Klebeband 19 mm×10 mm, manufactured by tesa) was attached to the line image and slowly peeled off. After peeling, the image was observed visually and with a microscope, and the number of defects was used as the evaluation criterion. The fewer the defects, the better the adhesion of the toner to paper. The evaluation results are shown in Table 5. It is determined that the effect of the present disclosure is obtained if the number of defects is 5 or less.
[0159] (Evaluation 3) Fixability Evaluation 3 (Toner Scattering: Density Unevenness after Fixation) The experiment was carried out in an environment of 23°C and 50% RH. The media used was A4 color laser copy paper (Canon, 70 g / m 2 ) was used. The image forming device used was a commercially available LBP-3100 (Canon) that had been modified to change the print speed from 16 pages / minute to 40 pages / minute and had the fixing unit removed. For fixing the unfixed images, a modified fixing unit was used that had been modified so that the fixing temperature could be adjusted. Using this image forming apparatus, the toner amount on the paper was set to 9 g / m 2 After adjusting the density so that the density was 5.0%, a solid black image was printed in an unfixed state, and the unfixed image was fixed using the modified fixing device. The image density was measured at 10 randomly selected points on the fixed image, and the lowest measured value was subtracted from the highest measured value among the measured values obtained, and the density difference was evaluated based on the percentage. The smaller the density difference, the more toner scattering was suppressed, and it was determined that the performance was excellent. The density was measured using a Macbeth reflection densitometer (manufactured by Macbeth Co., Ltd.). It was determined that the effect of the present disclosure was obtained if the density difference was 5.0% or less.
[0160] <Example 2> The image forming apparatus was changed to an HP LaserJet Enterprise M653x modified in the same manner as the LBP-3100 used in Example 1, and the toner was changed as shown in Table 5. Except for this, the evaluation was performed in the same manner as in Example 1.
[0161] <Examples 3 to 9> Except for changing the toner as shown in Table 5, the same evaluation as in Example 1 was carried out.
[0162] <Example 10> The image forming apparatus was changed to a color copier iRC-3200 (manufactured by Canon) modified in the same manner as the LBP-3100 used in Example 1, and the evaluation was performed in the same manner as in Example 1, except that the toner was changed as shown in Table 5.
[0163] <Examples 11 to 18> Except for changing the toner as shown in Table 5, the same evaluation as in Example 1 was carried out. Incidentally, toners 4, 6, 9, 10, 14, 15, 17 and 18 (Examples 4, 6, 9, 10, 14, 15, 17 and 18) were evaluated as reference examples.
[0164] <Comparative Examples 1 to 3> Except for changing the toner as shown in Table 6, the same evaluation as in Example 1 was carried out.
[0165] <Comparative Examples 4 and 5> The image forming apparatus was changed to an HP LaserJet Enterprise M653x modified in the same manner as the LBP-3100 used in Example 1, and the toner was changed as shown in Table 6. Except for this, the evaluation was performed in the same manner as in Example 1.
[0166] <Comparative Examples 6 and 7> Except for changing the toner as shown in Table 6, the same evaluation as in Example 1 was carried out.
[0167] <Comparative Example 8> The image forming apparatus was changed to a color copier iRC-3200 (manufactured by Canon) modified in the same manner as the LBP-3100 used in Example 1, and the evaluation was performed in the same manner as in Example 1, except that the toner was changed as shown in Table 6.
[0168] [Table 5]
[0169] [Table 6] [Explanation of symbols]
[0170] 1. Domain of release agent, 2. Domain of crystalline polyester, 3: From the outline of the cross section of the toner particle Then, a boundary line of 25% of the distance between the center point of the contour and the cross section
Claims
1. A toner containing toner particles having a polyester resin, the softening point of the toner measured by a constant load extrusion type capillary rheometer is 150° C. or lower; the toner particles have the polyester resin within 100 nm from the surface of the toner particles, the polyester resin is an amorphous polyester resin, The toner particles are A core containing a styrene-acrylic resin and an ester wax; and A shell containing only the amorphous polyester resin having a core-shell structure having The shell covers the core, In a cross section of the toner observed with a transmission electron microscope, The thickness of the shell is 100 nm or more and 200 nm or less, the content of the ester wax is 5.00 parts by mass or more and 50 parts by mass or less relative to 100 parts by mass of the styrene-acrylic resin, the content ratio of the monomer unit represented by the following formula (B) in the amorphous polyester resin is 30.0 mass % or more and 50.0 mass % or less with respect to the mass of the amorphous polyester resin, the content ratio of the monomer unit represented by the following formula (C) in the amorphous polyester resin is 25.0 mass % or more and 50.0 mass % or less with respect to the mass of the amorphous polyester resin, the content ratio of the monomer unit represented by the following formula (D) in the amorphous polyester resin is 1.0 mass% or more and 50.0 mass% or less with respect to the mass of the amorphous polyester resin, 【Chemistry 1】 (In formula (B), R 1 represents a benzene ring.) 【Chemistry 2】 (In formula (C), R 2 represents an ethylene group or a propylene group, x and y each represent an integer of 1 or more, and the average value of x+y in the polyester resin is 2 to 10.) 【Chemistry 3】 (In formula (D), R 3 represents an ethylene group or a propylene group.) the amount of ions is measured from the surface of the toner particles to a depth of 100 nm by time-of-flight secondary ion mass spectrometry, and the amount of counted ions having a structure represented by the following formula (A) is divided by the total amount of ions counted to obtain a standard value, and one or more peaks of the standard value are present within a range of 100 nm from the surface of the toner particles, When the standard value of the peak having the maximum standard value among the one or more peaks is defined as A(dmax) and the standard value on the surface of the toner particle is defined as A(0), the A(dmax) and the A(0) satisfy the following formulas (1) and (2): A toner characterized by: 1.15≦A(dmax) / A(0)≦5.00 (1) 0.010≦A(0) (2) 【Chemistry 4】
2. 2. The toner according to claim 1, wherein, when a standard value at a depth of 100 nm from a surface of the toner particle is defined as A(100), A(dmax) and A(100) satisfy the following formula (3): 1.15≦A(dmax) / A(100)≦5.00 (3)
3. The toner described in claim 2, wherein A(100) satisfies the following formula (5): 0.010≦A(100)≦0.100 (5)
4. 4. The toner according to claim 1, wherein the polyester resin has a dielectric loss tangent at 25° C. and 10,000 Hz of 0.0070 or more and 0.0140 or less.
5. The toner according to any one of claims 1 to 4, wherein A(0) satisfies the following formula (4): 0.010≦A(0)≦0.100 (4)
6. when acetonitrile is used as a poor solvent and chloroform is used as a good solvent for the chloroform-soluble fraction of the polyester resin, and the mobile phase is changed linearly from a mobile phase composition of 100% by mass of acetonitrile to a mobile phase composition of 100% by mass of chloroform, two or more peaks are obtained when the eluted components are analyzed by gradient polymer elution chromatography, The toner according to any one of claims 1 to 5, wherein when a standard value of a peak showing the maximum peak intensity among the two or more peaks is S(1) and a standard value of a peak showing the second maximum peak intensity is S(2), the S(1) and the S(2) satisfy the following formula (6): 0.40≦S(2) / S(1)<1.00 (6)
7. 7. The toner according to claim 1, wherein the content of the polyester resin is 1.0 part by mass or more and 10.0 parts by mass or less with respect to 100 parts by mass of the styrene-acrylic resin.
8. In a cross section of the toner observed with a transmission electron microscope, The average number of domains of the ester wax is 8 or more and 500 or less, the number average major axis of the domains of the ester wax is 50 nm or more and 300 nm or less; 8. The toner according to claim 1, wherein a ratio of the domains present in an area from a contour of the cross section to 25% or less of a distance between the contour and a geometric center of the cross section is 60% by number or more and 100% by number or less with respect to the total number of domains present in the cross section.
9. The toner according to claim 1, wherein R 2 in formula (C) represents a propylene group, and R 3 in formula (D) represents an ethylene group.
10. The toner according to claim 9, wherein the average value of x+y in the polyester resin is 2.
Citation Information
Patent Citations
Polyester resin composition, resin composition for electrophotographic toner, and electrophotographic toner
JP2013203857A
Toner
JP2016142758A
Toner and image forming method
JP2016142760A
Toner
JP2017044982A
Toner
JP2017107169A